Quality evaluation method of negative electrode, manufacturing method of lithium secondary battery, negative electrode, and lithium secondary battery
Patent Information
- Application Number
- KR1020250027120
- Authority / Receiving Office
- KR · KR
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-02-28
- Publication Date
- 2026-09-04
Smart Images

Figure PAT00001_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a method for evaluating the quality of a negative electrode, a method for manufacturing a lithium secondary battery comprising the step of evaluating the quality of the negative electrode according to the method, a negative electrode, and a lithium secondary battery. Background Technology
[0003] Due to their high energy density and long lifespan, lithium-ion batteries have established themselves as essential energy storage devices in various applications, including electric vehicles, energy storage systems, and small electronic devices. In particular, the high capacity of lithium-ion batteries is a critical requirement for electric vehicles and large-scale energy storage systems that demand extended operation; consequently, continuous research is being conducted to advance the design of active materials and battery manufacturing technologies to meet these requirements.
[0004] Conventionally, lithium secondary batteries mainly used graphite-based anode active materials as anode active materials, but recently, there has been a growing demand for silicon-based anode active materials that can achieve high capacity characteristics with a theoretical capacity about six times higher than that of conventional graphite.
[0005] However, silicon-based active materials exhibit significant volume changes when lithium ions are inserted and extracted during the charging and discharging process, leading to internal stress between the negative electrode active material layer and the negative electrode current collector. If this internal stress accumulates in the negative electrode, it can cause wrinkling or delamination at the interface between the active material layer and the current collector, resulting in a degradation of the safety and lifespan characteristics of the lithium secondary battery. Therefore, development is underway for negative electrodes capable of suppressing wrinkling and / or delamination during charging and discharging, even when silicon-based active materials are included.
[0006] Conventionally, methods have primarily been developed to verify whether wrinkles and / or delamination will occur in a cathode containing a silicon-based cathode active material by manufacturing a half-cell or a full cell using the cathode. However, this approach has the disadvantage of being inefficient in terms of cost and time, as a cell must be manufactured every time a cathode is designed.
[0007] Therefore, there is a need to develop a technology that can design the cathode by efficiently predicting whether delamination and / or wrinkling will occur, without manufacturing the cell. The problem to be solved
[0009] The present invention aims to provide a method for evaluating the quality of a cathode that can efficiently assess whether detachment and wrinkling occur in the cathode through a simple adhesion measurement of the cathode during the cathode manufacturing stage.
[0010] The present invention aims to provide a method for manufacturing a lithium secondary battery using a cathode evaluated as a good product by the cathode quality evaluation method.
[0011] The present invention aims to solve the above-mentioned problems by designing a cathode such that an adhesion index value capable of predicting whether delamination and / or wrinkling of the cathode will occur before cell manufacturing satisfies a specific range, thereby providing a cathode in which wrinkling and / or delamination are suppressed during charging and discharging, and a lithium secondary battery including the same. means of solving the problem
[0013] [1] The present invention provides a method for evaluating the quality of a cathode, comprising the steps of: preparing a cathode comprising a cathode current collector and a cathode active material layer located on the cathode current collector and comprising a silicon-based cathode active material (S1); measuring an adhesion force F1 between the cathode current collector and the cathode active material layer (S2); immersing the cathode in liquid nitrogen and then measuring an adhesion force F2 between the cathode current collector and the cathode active material layer (S3); and evaluating the quality of the cathode by evaluating the adhesion index value defined by the following formula 1 as good if it is greater than or equal to a reference value, and as defective if it is less than the reference value (S4).
[0014] [Equation 1]
[0015] Adhesion Index (Unit: gf) = F2 (Unit: gf) - F1 (Unit: gf)
[0016] [2] The present invention provides a method for evaluating the quality of a cathode, wherein the good product in [1] is a cathode having a risk level of 2 or less as defined by the following formula A.
[0017] [Equation A]
[0018] Risk Level = Talley Index + Wrinkle Index
[0019] In the above equation A,
[0020] The above delamination index and the above wrinkle index are measured by separating the negative electrode after charging the lithium secondary battery comprising the negative electrode, positive electrode, and electrolyte of the above S1 step to 100% SOC, wherein the delamination index is 3 if delamination occurs in 50% or more of the interface area between the negative electrode active material layer and the negative electrode current collector, 2 if delamination occurs in 10% to 50% of the interface area between the negative electrode active material layer and the negative electrode current collector, 1 if delamination occurs in 0.1% to 10% of the interface area between the negative electrode active material layer and the negative electrode current collector, and 0 if delamination occurs in 0.1% or less of the interface area between the negative electrode active material layer and the negative electrode current collector, and the above wrinkle index is 3 if wrinkles occur in 50% or more of the surface area of the negative electrode active material layer, and 2 if wrinkles occur in 10% to 50% of the surface area of the negative electrode active material layer, and the surface area of the negative electrode active material layer If wrinkles occur in 0.1% to 10%, it is 1, and if wrinkles occur in 0.1% or less of the surface area of the negative electrode active material layer, it is 0.
[0021] [3] The present invention provides a method for evaluating the quality of a cathode, wherein the good product in [2] is a cathode having a delamination index of 1 or less.
[0022] [4] The present invention provides a method for evaluating the quality of a cathode, wherein the good product in [2] or [3] is a cathode having a wrinkle index of 1 or less.
[0023] [5] The present invention provides a method for evaluating the quality of a cathode, wherein, in at least one of [1] to [4], the reference value is obtained by performing the following steps: preparing a plurality of cathode specimens including a cathode current collector and a cathode active material layer located on the cathode current collector and including a silicon-based cathode active material; measuring the adhesion force F1 between the cathode current collector and the cathode active material layer for each of the plurality of cathode specimens; immersing each of the plurality of cathode specimens in liquid nitrogen and then measuring the adhesion force (F2) between the cathode current collector and the cathode active material layer; and deriving a reference value from a database obtained by measuring the adhesion index defined by Equation 1 and the risk level defined by Equation A for each of the plurality of cathode specimens.
[0024] [Equation A]
[0025] Risk Level = Talley Index + Wrinkle Index
[0026] In the above Equation A, the delamination index and the wrinkle index are measured by separating each of the plurality of negative electrode specimens and measuring the lithium secondary battery, which includes the anode and electrolyte, after charging each of the negative electrode specimens to SOC 100%; the delamination index is 3 if delamination occurs in 50% or more of the interface area between the negative electrode active material layer and the negative electrode current collector, 2 if delamination occurs in 10% to 50% of the interface area between the negative electrode active material layer and the negative electrode current collector, 1 if delamination occurs in 0.1% to 10% of the interface area between the negative electrode active material layer and the negative electrode current collector, and 0 if delamination occurs in 0.1% or less of the interface area between the negative electrode active material layer and the negative electrode current collector; the wrinkle index is 3 if wrinkles occur in 50% or more of the surface area of the negative electrode active material layer, and 2 if wrinkles occur in 10% to 50% of the surface area of the negative electrode active material layer; and the negative electrode If wrinkles occur in 0.1% to 10% of the surface area of the active material layer, it is 1, and if wrinkles occur in 0.1% or less of the surface area of the negative active material layer, it is 0.
[0027] [6] The present invention provides a method for evaluating the quality of a cathode, wherein, in [5], the reference value is set to the minimum value among the adhesion strength indices of cathode specimens in which the risk level satisfies the target range in the database.
[0028] [7] The present invention provides a method for evaluating the quality of a cathode, wherein, in [6] above, the target range is such that the risk level is 2 or less.
[0029] [8] The present invention provides a method for evaluating the quality of a cathode, wherein in at least one of [1] to [7], the S3 step involves immersing the cathode in liquid nitrogen at -210°C to -180°C and then measuring the adhesion force (F2) between the cathode current collector and the cathode active material layer.
[0030] [9] The present invention provides a method for evaluating the quality of a cathode, wherein in at least one of [1] to [8], the S3 step involves immersing the cathode in liquid nitrogen for 5 to 15 minutes and then measuring the adhesion force (F2) between the cathode current collector and the cathode active material layer.
[0031]
[10] The present invention provides a method for evaluating the quality of a cathode, wherein, in at least one of [1] to [9], the silicon-based cathode active material comprises a Si / C composite.
[0032]
[11] The present invention provides a method for evaluating the quality of a cathode, wherein, in at least one of [1] to
[10] , the silicon-based cathode active material is included in an amount of 5 to 15 weight percent based on the total weight of the cathode active material layer.
[0033]
[12] The present invention provides a method for manufacturing a lithium secondary battery comprising: a step of manufacturing a cathode comprising a cathode current collector and a cathode active material layer located on the cathode current collector and comprising a silicon-based cathode active material; a step of evaluating the quality of the cathode according to any one of [1] to
[11] ; and a step of manufacturing a lithium secondary battery comprising a cathode evaluated as good and a positive electrode facing the cathode.
[0034]
[13] The present invention provides a method for manufacturing a lithium secondary battery, wherein the cathode in
[12] has a risk level of 2 or less as defined by the following formula A.
[0035] [Equation A]
[0036] Risk Level = Talley Index + Wrinkle Index
[0037] In the above Equation A, the delamination index and the wrinkle index are measured by separating the negative electrode after charging the lithium secondary battery comprising the negative electrode, positive electrode, and electrolyte to 100% SOC, wherein the delamination index is 3 if delamination occurs in 50% or more of the interface area between the negative electrode active material layer and the negative electrode current collector, 2 if delamination occurs in 10% to 50% of the interface area between the negative electrode active material layer and the negative electrode current collector, 1 if delamination occurs in 0.1% to 10% of the interface area between the negative electrode active material layer and the negative electrode current collector, and 0 if delamination occurs in 0.1% or less of the interface area between the negative electrode active material layer and the negative electrode current collector; and the wrinkle index is 3 if wrinkles occur in 50% or more of the surface area of the negative electrode active material layer, 2 if wrinkles occur in 10% to 50% of the surface area of the negative electrode active material layer, and the surface area of the negative electrode active material layer If wrinkles occur in 0.1% to 10%, it is 1, and if wrinkles occur in 0.1% or less of the surface area of the negative electrode active material layer, it is 0.
[0038]
[14] The present invention provides a method for manufacturing a lithium secondary battery, wherein, in
[12] or
[13] , the silicon-based negative electrode active material comprises a Si / C composite.
[0039]
[15] The present invention provides a method for manufacturing a lithium secondary battery, wherein, in at least one of
[12] to
[14] , the silicon-based negative electrode active material is included in an amount of 5 to 15 weight percent based on the total weight of the negative electrode active material layer.
[0040]
[16] The present invention provides a cathode comprising: a cathode current collector; and a cathode active material layer located on the cathode current collector and comprising a silicon-based cathode active material, wherein the adhesion index value defined by Formula 1 below is 4.0 gf or higher.
[0041] [Equation 1]
[0042] Adhesion index (unit: gf) = F2 - F1
[0043] In the above Equation 1, F1 (unit: gf) is the adhesion force between the negative current collector and the negative active material layer, and F2 (unit: gf) is the adhesion force between the negative current collector and the negative active material layer after immersing the negative electrode in liquid nitrogen.
[0044]
[17] The present invention provides a cathode in which the silicon-based cathode active material of
[16] comprises a Si / C composite.
[0045]
[18] The present invention provides a cathode in which, in
[16] or
[17] , the silicon-based cathode active material is included in an amount of 5% to 15% by weight based on the total weight of the cathode active material layer.
[0046]
[19] The present invention provides a cathode in which, in at least one of
[16] to
[18] , the risk level defined by the following formula A is 2 or less.
[0047] [Equation A]
[0048] Risk Level = Talley Index + Wrinkle Index
[0049] In the above Equation A, the delamination index and the wrinkle index are measured by separating the negative electrode after charging the lithium secondary battery comprising the negative electrode, positive electrode, and electrolyte to 100% SOC, wherein the delamination index is 3 if delamination occurs in 50% or more of the interface area between the negative electrode active material layer and the negative electrode current collector, 2 if delamination occurs in 10% to 50% of the interface area between the negative electrode active material layer and the negative electrode current collector, 1 if delamination occurs in 0.1% to 10% of the interface area between the negative electrode active material layer and the negative electrode current collector, and 0 if delamination occurs in 0.1% or less of the interface area between the negative electrode active material layer and the negative electrode current collector; and the wrinkle index is 3 if wrinkles occur in 50% or more of the surface area of the negative electrode active material layer, 2 if wrinkles occur in 10% to 50% of the surface area of the negative electrode active material layer, and the surface area of the negative electrode active material layer If wrinkles occur in 0.1% to 10%, it is 1, and if wrinkles occur in 0.1% or less of the surface area of the negative electrode active material layer, it is 0.
[0050]
[20] The present invention provides a cathode in which the talc index of
[19] is 1 or less.
[0051]
[21] The present invention provides a cathode in which the wrinkle index is 1 or less, in the above
[19] or
[20] .
[0052]
[22] The present invention provides a lithium secondary battery comprising a cathode, an anode, and an electrolyte according to any one of
[16] to
[21] . Effects of the invention
[0054] The quality evaluation method for a cathode according to the present invention measures the adhesion strength F1 between a cathode current collector and a cathode active material layer for a prepared cathode, and then measures the adhesion strength F2 between the cathode current collector and the cathode active material layer after immersing the cathode in liquid nitrogen. If the adhesion strength index, defined as the value obtained by subtracting F1 from F2, is greater than or equal to a reference value, it is evaluated as a good product, and if it is less than the reference value, it is evaluated as a defective product. Accordingly, the quality evaluation method for a cathode according to the present invention can evaluate whether detachment and wrinkling will occur in a designed cathode after charging and discharging simply by measuring the adhesion strength index of the cathode during the manufacturing stage of the cathode before manufacturing a lithium secondary battery after designing the cathode. As a result, the step of separately manufacturing a lithium secondary battery for each designed cathode can be omitted, allowing the quality evaluation of the cathode to be carried out very efficiently in terms of cost and time, and the defect rate of the manufactured lithium secondary battery can be significantly reduced.
[0055] The method for manufacturing a lithium secondary battery according to the present invention can reduce the occurrence rate of delamination and wrinkling occurring in the negative electrode during charging and discharging by manufacturing a lithium secondary battery using a negative electrode evaluated as a good product according to the negative electrode quality evaluation method, and thereby improve the safety and lifespan characteristics of the lithium secondary battery.
[0056] The cathode according to the present invention comprises a silicon-based cathode active material and is characterized by an adhesion strength index defined as the difference in adhesion strength before and after immersion in liquid nitrogen satisfying a specific range. By designing the cathode according to the present invention such that the adhesion strength index satisfies a specific range while comprising a silicon-based cathode active material, wrinkles and delamination caused by volume changes of the silicon-based cathode active material during charging and discharging of a lithium secondary battery comprising the cathode can be suppressed.
[0057] The lithium secondary battery according to the present invention may have excellent safety and lifespan characteristics by including the negative electrode. Brief explanation of the drawing
[0059] Figure 1 is a flowchart of a method for evaluating the quality of a cathode according to the present invention. FIG. 2 is an exploded assembly diagram of a lithium secondary battery according to one embodiment of the present invention. Figure 3 is an image showing whether wrinkles and detachment occurred on the cathode after performing charge and discharge on a lithium secondary battery manufactured using the cathode manufactured in the reference example. Figure 4 is an image showing whether wrinkles and detachment occurred on the cathode after performing charge and discharge on a lithium secondary battery manufactured using the cathode manufactured in Manufacturing Example 1. Figure 5 is an image showing whether wrinkles and detachment occurred on the cathode after performing charge and discharge on a lithium secondary battery manufactured using the cathode manufactured in Example 2. Figure 6 is an image showing whether wrinkles and detachment occurred on the cathode after performing charge and discharge on a lithium secondary battery manufactured using the cathode manufactured in Example 3. Figure 7 is an image showing whether wrinkles and detachment occurred on the cathode after performing charge and discharge on a lithium secondary battery manufactured using the cathode manufactured in Example 4. Figure 8 is an image showing whether wrinkles and detachment occurred on the cathode after performing charge and discharge on a lithium secondary battery manufactured using the cathode prepared in Preparation Example 5. Figure 9 is an image showing whether wrinkles and detachment occurred on the cathode after performing charge and discharge on a lithium secondary battery manufactured using the cathode prepared in Preparation Example 6. Figure 10 is an image showing whether wrinkles and detachment occurred on the cathode after performing charge and discharge on a lithium secondary battery manufactured using the cathode prepared in Example 7. Figure 11 is an image showing whether wrinkles and detachment occurred on the cathode after performing charge and discharge on a lithium secondary battery manufactured using the cathode manufactured in Example 8. Figure 12 is an image showing whether wrinkles and detachment occurred on the cathode after performing charge and discharge on a lithium secondary battery manufactured using the cathode manufactured in Example 9. Specific details for implementing the invention
[0060] The present invention will be described in more detail below.
[0061] Terms and words used in this specification and claims should not be interpreted as being limited to their ordinary or dictionary meanings, but should be interpreted in a meaning and concept consistent with the technical spirit of the invention, based on the principle that the inventor can appropriately define the concept of the terms to best describe his invention.
[0062] The terms used in this specification are used merely to describe exemplary embodiments and are not intended to limit the invention. The singular expression includes the plural expression unless the context clearly indicates otherwise.
[0063] In this specification, terms such as “comprising,” “having,” or “having” are intended to specify the existence of the implemented features, numbers, steps, components, or combinations thereof, and should be understood as not excluding in advance the existence or addition of one or more other features, numbers, steps, components, or combinations thereof.
[0064] In this specification, “risk level” refers to a parameter defined by the following formula A. The risk level is a parameter that evaluates the safety of a lithium secondary battery by quantifying the degree of delamination occurring at the interface between the negative electrode active material layer and the negative electrode current collector and the degree of wrinkling occurring on the negative electrode after performing charge and discharge on the lithium secondary battery.
[0065] [Equation A]
[0066] Risk Level = Talley Index + Wrinkle Index
[0067] In the above formula A, the delamination index and the wrinkle index may be measured by separating the negative electrode after charging a lithium secondary battery comprising a negative electrode, a positive electrode, and an electrolyte to 100% SOC. Specifically, the delamination index and the wrinkle index may be measured by separating the negative electrode after charging a lithium secondary battery comprising a negative electrode, a positive electrode, and an electrolyte to 100% SOC (0.05C cut-off) at 25°C with CC / CV and a 0.2C-rate. At this time, the anode may be prepared by mixing lithium cobalt oxide as the anode active material, carbon black as the anode conductive material, and polyvinylidene fluoride (PVDF) as the anode binder in a weight ratio of 97.6:1.1:1.3 to prepare an anode slurry, applying the anode slurry onto an anode current collector, and drying it. The electrolyte may be prepared by dissolving 1.2M LiPF6 in an organic solvent mixed with ethylene carbonate (EC):polycarbonate (PC):ethylpropionate (EP):polypropylene (PP) in a volume ratio of 20:10:25:45.
[0068] The above delamination index can be measured by visually observing the delamination occurring at the interface between the cathode active material layer and the cathode current collector in the cathode to be measured. The above delamination index is 3 if delamination occurs at 50% or more of the interface area between the cathode active material layer and the cathode current collector, 2 if delamination occurs at 10% to 50% of the interface area between the cathode active material layer and the cathode current collector, 1 if delamination occurs at 0.1% to 10% of the interface area between the cathode active material layer and the cathode current collector, and 0 if delamination occurs at 0.1% or less of the interface area between the cathode active material layer and the cathode current collector.
[0069] The above wrinkle index can be measured by visually observing wrinkles occurring at the interface between the cathode active material layer and the cathode current collector at the cathode to be measured. The above wrinkle index is 3 if wrinkles occur in 50% or more of the surface area of the cathode active material layer, 2 if wrinkles occur in 10% to 50% of the surface area of the cathode active material layer, 1 if wrinkles occur in 0.1% to 10% of the surface area of the cathode active material layer, and 0 if wrinkles occur in 0.1% or less of the surface area of the cathode active material layer.
[0070] In this specification, the “Si / C composite” may be a silicon-based negative electrode active material having a form in which nano-sized silicon particles are evenly dispersed within a carbon (C) matrix. Specifically, in this specification, the term “composite” refers to a material in which two or more materials are combined to form physically and chemically different phases, thereby exhibiting more effective functions. The “Si / C composite” does not refer to a state in which Si and carbon (C) are simply aggregated or mixed, but rather refers to a state in which silicon particles are embedded within a carbon matrix.
[0071] In this specification, "loading amount (unit: g / 25cm 2 )" is 25cm 2 This refers to the mass (g) of the electrode active material layer contained per area. After punching out the electrode to a size of 5cm x 5cm, the weight W1 of the punched area and the weight W2 of the electrode current collector are measured. If the electrode active material layer is formed on both sides of the electrode current collector, it can be measured by substituting into [Equation 2-1] below, and if the electrode active material layer is formed on one side of the electrode current collector, it can be measured by substituting into [Equation 2-2] below.
[0072] [Equation 2-1] Loading amount (g / 25cm) 1 ) = (W1-W2) / 2
[0073] [Equation 2-2] Loading amount (g / 25cm) 1 ) = W1-W2
[0074] The present invention will be described in detail below.
[0076] The method for evaluating the quality of a negative electrode, the method for manufacturing a lithium secondary battery, the negative electrode, and the lithium secondary battery according to the present invention comprise at least one of the configurations disclosed below, and may comprise any combination of technically feasible configurations among the configurations below.
[0079] Cathode quality evaluation method
[0080] A method for evaluating the quality of a cathode according to the present invention comprises: a step (S1) of preparing a cathode comprising a cathode current collector and a cathode active material layer located on the cathode current collector and comprising a silicon-based cathode active material; a step (S2) of measuring an adhesion force F1 between the cathode current collector and the cathode active material layer; a step (S3) of immersing the cathode in liquid nitrogen and then measuring an adhesion force F2 between the cathode current collector and the cathode active material layer; and a step (S4) of evaluating the quality of the cathode, wherein if the adhesion force index value defined by the following formula 1 is greater than or equal to a reference value, it is evaluated as a good product, and if it is less than the reference value, it is evaluated as a defective product.
[0081] [Equation 1]
[0082] Adhesion Index (Unit: gf) = F2 (Unit: gf) - F1 (Unit: gf)
[0084] The quality evaluation method for a negative electrode according to the present invention can evaluate whether a negative electrode is good based on the degree of wrinkling and / or delamination after charging and discharging during the manufacturing stage of the negative electrode before manufacturing a lithium secondary battery. That is, defective electrodes can be filtered out simply and quickly through adhesion measurement without manufacturing a lithium secondary battery, thereby allowing the quality evaluation of the negative electrode to be performed efficiently in terms of time and cost, and significantly reducing the defect rate of the manufactured lithium secondary battery. For example, the risk level quantified by the degree of delamination and wrinkling of the manufactured lithium secondary battery may be 2 or less.
[0086] Figure 1 is a flowchart of a method for evaluating the quality of a cathode according to the present invention.
[0087] With reference to FIG. 1 below, each step of the method for evaluating the quality of a cathode according to the present invention will be described in detail.
[0089] (1) S1 step: Preparation step of the cathode
[0090] First, a cathode is prepared comprising a cathode current collector and a cathode active material layer located on the cathode current collector and comprising a silicon-based cathode active material.
[0092] The above cathode can be prepared by coating a cathode active material layer slurry on one or both sides of a sheet-shaped cathode current collector and then rolling it.
[0093] The above coating can be achieved by applying a cathode active material layer slurry to one or both sides of a cathode current collector and then performing a first drying. The first drying serves to remove the solvent from the cathode active material layer slurry and can be performed at 30 to 110°C, 40 to 95°C, or 50 to 85°C for up to 2 hours or up to 1 hour.
[0094] After the above rolling, a second drying step can be additionally performed.
[0095] The second drying above may be performed at 60 to 120°C, 70 to 110°C, or 60 to 100°C for 12 hours or more. When dried within the above range, the accuracy of the quality evaluation method of the cathode according to the present invention may be further increased.
[0096] The above-mentioned negative electrode active material layer slurry can be prepared by dispersing a silicon-based negative electrode active material in a solvent such as distilled water, ethanol, methanol, or isopropyl alcohol.
[0097] Alternatively, the cathode may be prepared by casting a cathode active material layer slurry onto a separate support and then laminating the film obtained by peeling off from the support onto a cathode current collector.
[0098] The above-mentioned cathode can be prepared by various methods in addition to the cathode preparation method described above.
[0100] As the above-mentioned cathode current collector, cathode current collectors generally used in the relevant technical field may be used, for example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, etc., and aluminum-cadmium alloy may be used. The above-mentioned cathode current collector may typically have a thickness of 3 μm to 500 μm, and fine irregularities may be formed on the surface of the above-mentioned cathode current collector to strengthen the bonding strength of the cathode active material. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.
[0103] The above-mentioned negative electrode active material layer is located on the negative electrode current collector. Specifically, the negative electrode active material layer may be located on one or both sides of the negative electrode current collector and may be composed of a single layer or multiple layers.
[0104] The above-mentioned negative electrode active material layer includes a silicon-based negative electrode active material.
[0105] Although silicon-based cathode active materials have superior theoretical capacity compared to carbon-based cathode active materials such as artificial graphite and natural graphite, they exhibit a large degree of volume expansion during charging and discharging, which can cause wrinkling and delamination in the cathode. For this reason, when a cathode is designed using a silicon-based cathode active material, it is important to evaluate whether wrinkling or delamination will occur during charging and discharging, unlike when a carbon-based cathode active material is used alone. Accordingly, the cathode quality evaluation method according to the present invention is performed particularly on a cathode containing a silicon-based cathode active material to select a cathode with excellent capacity characteristics and safety.
[0107] The above silicon-based negative electrode active material is silicon (Si) and silicon oxide (SiO₂).x (0 <x<2)로 표시될 수 있음) 및 Si / C 복합체(Si / C Composite)로 이루어진 군에서 선택된 적어도 1종을 포함할 수 있고, 바람직하게는 Si / C 복합체를 포함할 수 있다.
[0109] The silicon-based negative electrode active material may be included in an amount of 5 to 15 weight%, 7 to 13 weight%, or 8 to 12 weight% based on the total weight of the negative electrode active material layer. If the above range is satisfied, the accuracy of the quality evaluation method of the negative electrode according to the present invention may be superior.
[0111] The above-mentioned negative electrode active material layer may further include other negative electrode active materials in addition to the silicon-based negative electrode active material.
[0112] The above other negative electrode active material may be a compound capable of reversible intercalation and deintercalation of lithium in addition to a silicon-based negative electrode active material, and may be, for example, one or more selected from the group consisting of a carbon-based negative electrode active material, a metallic compound capable of alloying with lithium, and a metal oxide capable of doping and dedoping lithium. Specifically, the above carbon-based negative electrode active material may be one or more selected from the group consisting of artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon, or one or more selected from the group consisting of artificial graphite and natural graphite. The above metallic compound may be one or more selected from the group consisting of Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloy, Sn alloy, and Al alloy. The above metal oxide may be one or more selected from the group consisting of SnO2, vanadium oxide, and lithium vanadium oxide.
[0113] Preferably, the other negative electrode active material may be a carbon-based negative electrode active material.
[0114] The above other cathode active material may be included in an amount of 85 to 95 weight%, 87 to 93 weight%, or 88 to 92 weight% based on the total weight of the cathode active material layer.
[0116] The above cathode active material layer may further include a cathode conductive material.
[0117] A cathode conductive material is used to impart conductivity to the cathode, and in a battery being constructed, any material that possesses electronic conductivity without causing chemical changes can be used without any special limitations. Specifically, the cathode conductive material may include carbon-based materials such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, carbon fiber, carbon nanotube; metal powders or metal fibers such as copper, nickel, aluminum, or silver; conductive whiskers such as zinc oxide or potassium titanate; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives, and one of these alone or a mixture of two or more may be used.
[0118] The above-mentioned cathode conductive material may typically be included in an amount of 0.1 to 10 weight%, 0.1 to 8 weight%, or 0.1 to 5 weight% based on the total weight of the cathode active material layer.
[0119] The above cathode active material layer may further include a cathode binder.
[0120] The above-mentioned cathode binder serves to improve adhesion between cathode active material particles and adhesion between the cathode active material and the cathode current collector. Specifically, the above-mentioned cathode binder may include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer rubber (EPDM rubber), sulfonated-EPDM, styrene-butadiene rubber (SBR), fluororubber, acrylic acid, polyacrylamide, or various copolymers thereof, and one of these alone or a mixture of two or more may be used.
[0121] More specifically, the cathode binder may include a rubber-based (elastomer) binder and an acrylic-based binder. In this case, the adhesion between the cathode active material layer and the cathode current collector is appropriately improved, which may be advantageous for selecting a good quality cathode.
[0122] The above rubber-based binder may be one or more selected from the group consisting of styrene-butadiene rubber, sulfonated-EPDM, ethylene-propylene-diene monomer rubber (EPDM rubber), and fluororubber, or it may be styrene-butadiene rubber. By controlling the particle size and surface functional groups of the above rubber-based binder, the adhesion strength index defined by Formula 1 can be controlled.
[0123] The above acrylic binder may be one or more selected from the group consisting of polyacrylonitrile, acrylic acid, polyacrylamide, and copolymers thereof, or may be a copolymer of polyacrylonitrile, acrylic acid, and polyacrylamide. The copolymer of polyacrylonitrile, acrylic acid, and polyacrylamide can control the adhesion index of the cathode by appropriately adjusting the molar ratio between polyacrylonitrile, acrylic acid, and polyacrylamide.
[0124] The rubber-based binder and the acrylic-based binder may be included in a weight ratio of 4:6 to 6:4, 4.2:5.8 to 5.8:4.2, or 4.5:5.5 to 5.5:4.5. When the above ranges are satisfied, the adhesion strength index can be appropriately controlled, and it may be advantageous to select a good cathode.
[0125] The above-mentioned cathode binder may be included in an amount of 0.1 to 10 weight%, 0.5 to 10 weight%, 1 to 5 weight%, or 2 to 4 weight% based on the total weight of the cathode active material layer. When the above range is satisfied, the adhesion with the cathode current collector is adequately secured, and the energy density can be excellent.
[0126] The above cathode active material layer may further include a cathode additive. The above cathode additive may contribute to controlling the adhesion index defined by Equation 1.
[0127] The above cathode additive may include carboxymethyl cellulose. In this case, viscosity is imparted to the cathode active material layer to improve adhesion between cathode active material particles and between the cathode active material layer and the cathode current collector, and the dispersibility of the cathode active material layer can be increased.
[0128] The above cathode additive may be included in an amount of 0.1 to 2 weight%, 0.2 to 1 weight%, or 0.3 to 0.7 weight% based on the total weight of the cathode active material layer. When the above range is satisfied, the adhesion index defined by Formula 1 can be controlled, and the additive can sufficiently perform its role while improving energy density.
[0130] The above cathode active material layer has a loading amount of 100 mg / 25 cm 2 Up to 400 mg / 25 cm 2 , 125mg / 25cm 2 Up to 300 mg / 25 cm 2 , 150mg / 25cm 2 Up to 250 mg / 25 cm 2 , or 180mg / 25cm 2 Up to 220 mg / 25 cm 2 It may be possible. If the above range is satisfied, the energy density is excellent, and the stress on the cathode can be relieved as the cathode active material layer expands in volume during charging and discharging.
[0132] The above-mentioned negative electrode active material layer may have a thickness of 30 to 100 μm, 40 to 90 μm, or 45 to 85 μm. When the above range is satisfied, sufficient capacitance characteristics can be achieved, and the stress on the negative electrode can be relieved as the negative electrode active material layer expands in volume during charging and discharging.
[0134] The above-mentioned negative electrode active material layer may have a porosity of 10 to 40%, 20 to 35%, or 22 to 32%. When the above ranges are satisfied, the energy density is excellent, and the stress on the negative electrode can be relieved as the negative electrode active material layer expands in volume during charging and discharging.
[0136] (2) S2 step: Adhesion between the negative current collector and the negative active material layer (F 1 ) Measurement step
[0137] Next, the adhesion force (F1) between the above-mentioned negative current collector and the above-mentioned negative active material layer is measured.
[0139] The above F1 can be measured by making a sample by punching a prepared cathode into 20mm × 125mm and attaching it to a slide glass with double-sided tape on the cathode side, loading the sample into a UTM, positioning the jig and the sample at a 90° angle, and measuring the average value of the flat section of the stress-strain curve. Preferably, the above F1 can be measured by the above method immediately after manufacturing the cathode, or after disassembling a lithium secondary battery containing the cathode and separating the cathode.
[0141] (3) S3 Step: Adhesion between the cathode current collector and the cathode active material layer after immersion in liquid nitrogen (F 2 ) Measurement step
[0142] Next, After immersing the above cathode in liquid nitrogen, the adhesion force (F2) between the cathode current collector and the cathode active material layer is measured. Specifically, after completely immersing the cathode in liquid nitrogen, the cathode can be recovered from the liquid nitrogen, dried, and F2 can be measured.
[0143] The above F2 can be measured as the average value of the flat section of the stress-strain curve by immersing the cathode in liquid nitrogen, then punching the cathode into a 20mm × 125mm shape, attaching it to a slide glass with double-sided tape with the cathode surface, loading the sample into a UTM, positioning the jig and the sample at a 90° angle, and measuring the sample.
[0145] The above cathode may be immersed in liquid nitrogen at -210°C to -180°C, -205°C to -185°C, -200°C to -190°C, or -198°C to -193°C. When immersed in liquid nitrogen within the above temperature ranges, sufficient internal stress can be achieved between the cathode current collector and the cathode active material layer due to the difference in the coefficient of thermal expansion.
[0146] The above cathode may be immersed in liquid nitrogen for 5 to 15 minutes, 7 to 13 minutes, or 8 to 12 minutes. When immersed in liquid nitrogen within the above time range, sufficient internal stress between the cathode current collector and the cathode active material layer can be achieved due to the difference in the coefficient of thermal expansion.
[0148] (4) S4 Step: Quality evaluation step of the cathode using the adhesion index
[0149] Next, the quality of the cathode is evaluated by evaluating the adhesion index value defined by the following Equation 1 as good if it is greater than or equal to the reference value, and as defective if it is less than the reference value.
[0150] [Equation 1]
[0151] Adhesion Index (Unit: gf) = F2 (Unit: gf) - F1 (Unit: gf)
[0153] The above adhesion index is a parameter indicating the level of adhesion degradation caused by internal stress between the negative electrode current collector and the negative electrode active material layer. The higher the value of the adhesion index, the lower the tendency for the occurrence of detachment and wrinkling to occur when a lithium secondary battery manufactured using the negative electrode is charged and discharged. Therefore, if a good product is evaluated based on an adhesion index above a reference value, a good product can be selected in which the occurrence of detachment and wrinkling of the negative electrode during charging and discharging is below a certain level.
[0155] The above reference value may be a value derived from a previously obtained database. The above reference value may have the unit of gf.
[0156] Specifically, the reference value can be obtained by performing the following steps: preparing a plurality of cathode specimens comprising a cathode current collector and a cathode active material layer located on the cathode current collector and comprising a silicon-based cathode active material; measuring the adhesion strength F1 between the cathode current collector and the cathode active material layer for each of the plurality of cathode specimens; immersing each of the plurality of cathode specimens in liquid nitrogen and then measuring the adhesion strength F2 between the cathode current collector and the cathode active material layer; and deriving the reference value from a database obtained by measuring the adhesion strength index defined by Equation 1 and the risk level defined by Equation A below for each of the plurality of cathode specimens.
[0157] [Equation A]
[0158] Risk Level = Talley Index + Wrinkle Index
[0159] In the above Equation A, the delamination index and the wrinkle index are measured by separating each of the plurality of negative electrode specimens and measuring the lithium secondary battery, which includes each of the plurality of negative electrode specimens, a positive electrode, and an electrolyte, after charging the battery to 100% SOC; the delamination index is 3 if delamination occurs in 50% or more of the interface area between the negative electrode active material layer and the negative electrode current collector, 2 if delamination occurs in 10% to 50% of the interface area between the negative electrode active material layer and the negative electrode current collector, 1 if delamination occurs in 0.1% to 10% of the interface area between the negative electrode active material layer and the negative electrode current collector, and 0 if delamination occurs in 0.1% or less of the interface area between the negative electrode active material layer and the negative electrode current collector; the wrinkle index is 3 if wrinkles occur in 50% or more of the surface area of the negative electrode active material layer, and 2 if wrinkles occur in 10% to 50% of the surface area of the negative electrode active material layer; and the negative electrode If wrinkles occur in 0.1% to 10% of the surface area of the active material layer, it is 1, and if wrinkles occur in 0.1% or less of the surface area of the negative active material layer, it is 0.
[0161] The plurality of cathode specimens described above may or may not have the same composition except that they include a cathode current collector and a cathode active material layer and contain a silicon-based cathode active material. In other words, since the standard value is not derived to be applicable only to cathodes of the same design as the cathode being evaluated, the cathode quality evaluation method according to the present invention can be universally used when evaluating the quality of cathodes of various designs.
[0162] The above plurality of cathode specimens may be five or more cathode specimens. If the above range is satisfied, a minimum level of accuracy can be guaranteed. The more measurements are performed on the maximum number of cathode specimens, the higher the accuracy of the reference value can be.
[0163] In the process of obtaining the above reference value, the step of measuring the adhesion force F1 between the cathode current collector and the cathode active material layer for each of the plurality of cathode specimens, and the step of measuring the adhesion force F2 between the cathode current collector and the cathode active material layer after immersing each of the plurality of cathode specimens in liquid nitrogen, can be performed in the same manner as the method described above.
[0165] The above database may represent the correlation between the adhesion index and the risk level by matching the adhesion index defined by Equation 1 and the risk level defined by Equation A obtained for each of the above cathode specimens. Accordingly, the adhesion index of the cathode satisfying a certain level of risk level can be identified, making it easy to derive a reference value that serves as a criterion for determining whether it is a good product.
[0166] The above database can be obtained by accumulating the adhesion index defined by Equation 1 and the risk level defined by Equation A obtained for each of the above cathode specimens in a storage system such as memory, and recording them as visual data such as tables or graphs.
[0168] From the above database, a reference value can be derived to determine whether the product is of good quality, where the degree of delamination and / or wrinkling of the negative electrode during charging and discharging is above a certain level.
[0170] The above reference value may be set as the minimum value of the adhesion index among the cathode specimens in the database whose risk level satisfies the target range. By appropriately setting the target range of the risk level based on the target risk level of the designed cathode and setting the reference value accordingly, the risk level of the cathode evaluated as a good product can satisfy the target range.
[0171] For example, the above target range may be a risk level of 2 or less. Since a lower risk level implies a tendency for the degree of delamination and wrinkling of the negative electrode during charging and discharging to be lower, if the risk level is 2 or less, the degree of wrinkling and / or delamination occurring in the negative electrode during charging and discharging is lowered to some extent, thereby ensuring the safety and lifespan characteristics of the manufactured lithium secondary battery at a certain level or higher.
[0172] Alternatively, the above target range may be such that the risk level is 2 or less, the delamination index is 1 or less, and the wrinkle index is 1 or less. In this case, the case where either the wrinkle index or the delamination index is 2 can be prevented, so that the degree of both wrinkles and delamination may be low during charging and discharging of the cathode evaluated as a good product.
[0174] The above-mentioned good product can satisfy the target range for the risk level when setting the reference value. Accordingly, a cathode having the target risk level can be selected when designing the cathode.
[0175] The above-mentioned good product may be a negative electrode with a risk level of 2 or less, 1 or less, or 0. Accordingly, when the manufactured lithium secondary battery is charged and discharged, the degree of wrinkling and delamination on the negative electrode is low, so a negative electrode with excellent lifespan characteristics and stability of the lithium secondary battery can be selected.
[0176] The above-mentioned good product may have a delamination index of 1 or less, or 0. In this case, the cathode selected as a good product may experience delamination at a very low level during charging and discharging.
[0177] The above-mentioned good product may have a wrinkle index of 1 or less, or 0. In this case, the cathode selected as a good product may experience very low levels of detachment during charging and discharging.
[0179] Method for manufacturing a lithium secondary battery
[0180] A method for manufacturing a lithium secondary battery according to the present invention comprises: a step of manufacturing a negative electrode comprising a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector and comprising a silicon-based negative electrode active material; a step of evaluating the quality of the negative electrode using the aforementioned method for evaluating the quality of the negative electrode; and a step of manufacturing a lithium secondary battery comprising a negative electrode evaluated as good and a positive electrode facing the negative electrode.
[0182] A lithium secondary battery manufactured according to the above method for manufacturing a lithium secondary battery may have excellent lifespan characteristics and safety, as the degree of wrinkling and detachment of the negative electrode is low when performing charging and discharging.
[0184] Hereinafter, a method for manufacturing a lithium secondary battery according to the present invention will be described in detail.
[0186] (1) Manufacturing step of the cathode
[0187] A cathode is manufactured comprising a cathode current collector and a cathode active material layer located on the cathode current collector and comprising a silicon-based cathode active material.
[0189] The above cathode can be manufactured by applying a cathode active material layer slurry to one or both sides of a sheet-shaped cathode current collector, drying it, and then rolling it.
[0190] The above-mentioned negative electrode active material layer slurry can be prepared by dispersing a silicon-based negative electrode active material in a solvent such as distilled water, ethanol, methanol, or isopropyl alcohol.
[0191] The above cathode active material layer slurry is 100 mg / 25 cm 2 Up to 400 mg / 25 cm 2 , 125mg / 25cm 2 Up to 300 mg / 25 cm 2 , 150mg / 25cm 2 Up to 250 mg / 25 cm 2 , or 180mg / 25cm 2 Up to 220 mg / 25 cm 2 It can be applied with a loading amount.
[0192] The above drying can be performed by heat treatment at 30 to 110°C, 40 to 95°C, or 50 to 85°C for less than 2 hours or less than 1 hour. When the temperature and time during drying are within the above ranges, the cathode is dried without defects occurring, so the quality of the cathode can be excellent.
[0193] Alternatively, the cathode may be manufactured by casting a cathode active material layer slurry onto a separate support and then laminating the film obtained by peeling off from the support onto a cathode current collector.
[0194] The above-mentioned cathode can be manufactured by various methods in addition to the cathode preparation method described above.
[0196] As the above-mentioned cathode current collector, cathode current collectors generally used in the relevant technical field may be used, for example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, etc., and aluminum-cadmium alloy may be used. The above-mentioned cathode current collector may typically have a thickness of 3 μm to 500 μm, and fine irregularities may be formed on the surface of the above-mentioned cathode current collector to strengthen the bonding strength of the cathode active material. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.
[0198] The above-mentioned negative electrode active material layer includes a silicon-based negative electrode active material.
[0199] Conventionally, carbon-based negative electrode active materials were used as negative electrode active materials; however, because carbon-based negative electrode active materials have low capacity and a slow reaction rate with lithium, lithium secondary batteries using them had limitations in realizing high capacity characteristics and rapid charging performance. Accordingly, the present invention improves the capacity characteristics and rapid charging characteristics of a lithium secondary battery by including a silicon-based negative electrode active material with a high theoretical capacity and a fast reaction rate with lithium in the negative electrode active material layer.
[0201] The above silicon-based negative electrode active material is silicon (Si) and silicon oxide (SiO₂). x (0 <x<2)로 표시될 수 있음) 및 Si / C 복합체(Si / C Composite)로 이루어진 군에서 선택된 적어도 1종을 포함할 수 있고, 바람직하게는 Si / C 복합체를 포함할 수 있다.
[0202] When the above silicon-based negative electrode active material includes a Si / C composite, the degree of volume expansion during charging and discharging may be smaller compared to silicon, thereby suppressing the degradation of lifespan characteristics during charging and discharging, and the capacity characteristics and electrical conductivity may be superior compared to silicon oxide. Therefore, when the above first silicon-based negative electrode active material includes a Si / C composite, it has the advantage of improving cycle performance during rapid charging while realizing high capacity characteristics of a lithium secondary battery.
[0204] The above silicon-based negative electrode active material is D 50 This can be 5㎛ to 15㎛, 6㎛ to 11㎛, or 7㎛ to 9㎛. When the above range is satisfied, the cathode electrode density is increased, and high energy density can be achieved.
[0205] The silicon-based negative electrode active material may be included in an amount of 5 to 15 weight%, 7 to 13 weight%, or 8 to 12 weight% based on the total weight of the negative electrode active material layer. When the above range is satisfied, a balance can be achieved between capacity characteristics, rapid charging characteristics, and lifespan characteristics.
[0207] The above-mentioned negative electrode active material layer may further include other negative electrode active materials in addition to the silicon-based negative electrode active material.
[0208] The above other negative electrode active material may be a compound capable of reversible intercalation and deintercalation of lithium in addition to a silicon-based negative electrode active material, and may be, for example, one or more selected from the group consisting of a carbon-based negative electrode active material, a metallic compound capable of alloying with lithium, and a metal oxide capable of doping and dedoping lithium. Specifically, the above carbon-based negative electrode active material may be one or more selected from the group consisting of artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon, or one or more selected from the group consisting of artificial graphite and natural graphite. The above metallic compound may be one or more selected from the group consisting of Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloy, Sn alloy, and Al alloy. The above metal oxide may be one or more selected from the group consisting of SnO2, vanadium oxide, and lithium vanadium oxide.
[0209] Preferably, the other negative electrode active material may be a carbon-based negative electrode active material. In this case, problems caused by volume expansion of the silicon-based negative electrode active material can be mitigated, and adhesion to the current collector can be improved.
[0210] The above other cathode active material may be included in an amount of 85 to 95 weight%, 87 to 93 weight%, or 88 to 92 weight% based on the total weight of the cathode active material layer. When the above range is satisfied, the capacity characteristics are excellent and the lifespan characteristics can be improved.
[0212] The above cathode active material layer may further include a cathode conductive material.
[0213] A cathode conductive material is used to impart conductivity to the cathode, and in a battery being constructed, any material that possesses electronic conductivity without causing chemical changes can be used without any special limitations. Specifically, the cathode conductive material may include carbon-based materials such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, carbon fiber, carbon nanotube; metal powders or metal fibers such as copper, nickel, aluminum, or silver; conductive whiskers such as zinc oxide or potassium titanate; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives, and one of these alone or a mixture of two or more may be used.
[0214] The above-mentioned cathode conductive material may typically be included in an amount of 0.1 to 10 weight%, 0.1 to 8 weight%, or 0.1 to 5 weight% based on the total weight of the cathode active material layer.
[0215] The above cathode active material layer may further include a cathode binder.
[0216] The above-mentioned cathode binder serves to improve adhesion between cathode active material particles and adhesion between the cathode active material and the cathode current collector. Specifically, the above-mentioned cathode binder may include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer rubber (EPDM rubber), sulfonated-EPDM, styrene-butadiene rubber (SBR), fluororubber, acrylic acid, polyacrylamide, or various copolymers thereof, and one of these alone or a mixture of two or more may be used.
[0217] More specifically, the cathode binder may include an elastomer binder and an acrylic binder. In this case, it may be effective in suppressing the occurrence of wrinkling and delamination during charging and discharging while appropriately improving the adhesion between the cathode active material layer and the cathode current collector.
[0218] The above rubber-based binder may be one or more selected from the group consisting of styrene-butadiene rubber, sulfonated-EPDM, ethylene-propylene-diene monomer rubber (EPDM rubber), and fluororubber, or it may be styrene-butadiene rubber.
[0219] The above acrylic binder may be one or more selected from the group consisting of polyacrylonitrile, acrylic acid, polyacrylamide, and copolymers thereof, or may be a copolymer of polyacrylonitrile, acrylic acid, and polyacrylamide. The copolymer of polyacrylonitrile, acrylic acid, and polyacrylamide may satisfy the desired range of adhesion strength index by appropriately adjusting the molar ratio between polyacrylonitrile, acrylic acid, and polyacrylamide.
[0220] The rubber-based binder and the acrylic-based binder may be included in a weight ratio of 4:6 to 6:4, 4.2:5.8 to 5.8:4.2, or 4.5:5.5 to 5.5:4.5. When the above ranges are satisfied, the adhesion strength index may satisfy the desired range, and delamination and wrinkling occurring at the negative electrode during charging and discharging may be suppressed.
[0221] The above-mentioned cathode binder may be included in an amount of 0.1 to 10 weight%, 0.5 to 10 weight%, 1 to 5 weight%, or 2 to 4 weight% based on the total weight of the cathode active material layer. When the above range is satisfied, the adhesion with the cathode current collector is adequately secured, and the energy density can be excellent.
[0222] The above cathode active material layer may further include a cathode additive. The above cathode additive may contribute to controlling the adhesion index defined by Equation 1.
[0223] The above cathode additive may include carboxymethyl cellulose. In this case, viscosity is imparted to the cathode active material layer to improve adhesion between cathode active material particles and between the cathode active material layer and the cathode current collector, and the dispersibility of the cathode active material layer can be increased.
[0224] The above cathode additive may be included in an amount of 0.1 to 2 weight%, 0.2 to 1 weight%, or 0.3 to 0.7 weight% based on the total weight of the cathode active material layer. When the above range is satisfied, the adhesion index defined by Formula 1 can be controlled, and the additive can sufficiently perform its role while improving energy density.
[0226] The above cathode active material layer has a loading amount of 100 mg / 25 cm 2 Up to 400 mg / 25 cm 2 , 125mg / 25cm 2 Up to 300 mg / 25 cm 2 , 150mg / 25cm 2 Up to 250 mg / 25 cm 2 , or 180mg / 25cm 2 Up to 220 mg / 25 cm 2 It may be possible. If the above range is satisfied, the energy density is excellent, and the stress on the cathode can be relieved as the cathode active material layer expands in volume during charging and discharging.
[0228] According to the present invention, the thickness of the negative electrode active material layer may be 30 μm to 100 μm, 40 μm to 90 μm, or 45 μm to 85 μm. When the thickness of the active material layer is within the above range, the performance of the active material layer can be maximized while significantly reducing the defect rate of the electrode.
[0230] The above-mentioned negative electrode active material layer may have a porosity of 10 to 40%, 20 to 35%, or 22 to 32%. When the above ranges are satisfied, the energy density is excellent, and the stress on the negative electrode can be relieved as the negative electrode active material layer expands in volume during charging and discharging.
[0232] (2) Quality evaluation step of the cathode
[0233] Next, the quality of the cathode is evaluated using the cathode quality evaluation method according to the present invention.
[0235] The method for evaluating the quality of the above-mentioned cathode is the same as previously described, so a detailed explanation is omitted.
[0237] (3) Manufacturing steps of lithium secondary batteries
[0238] Next, a lithium secondary battery is manufactured comprising a negative electrode evaluated as good and a positive electrode facing the negative electrode. That is, the lithium secondary battery includes a negative electrode evaluated as good when the quality of the negative electrode is evaluated according to the negative electrode quality evaluation method.
[0239] The lithium secondary battery manufactured accordingly exhibits less delamination and wrinkling of the negative electrode during charging and discharging, which can result in excellent lifespan characteristics and safety, as well as a low defect rate.
[0241] The above cathode may have a risk level of 2 or less as defined by the following formula A.
[0242] [Equation A]
[0243] Risk Level = Talley Index + Wrinkle Index
[0244] In the above equation A,
[0245] The above delamination index and the above wrinkle index are measured by separating the negative electrode after charging the lithium secondary battery comprising the negative electrode, positive electrode, and electrolyte to 100% SOC, wherein the delamination index is 3 if delamination occurs in 50% or more of the interface area between the negative electrode active material layer and the negative electrode current collector, 2 if delamination occurs in 10% to 50% of the interface area between the negative electrode active material layer and the negative electrode current collector, 1 if delamination occurs in 0.1% to 10% of the interface area between the negative electrode active material layer and the negative electrode current collector, and 0 if delamination occurs in 0.1% or less of the interface area between the negative electrode active material layer and the negative electrode current collector; and the above wrinkle index is 3 if wrinkles occur in 50% or more of the surface area of the negative electrode active material layer, 2 if wrinkles occur in 10% to 50% of the surface area of the negative electrode active material layer, and 0.1% to It is 1 if wrinkles occur at 10%, and 0 if wrinkles occur at 0.1% or less of the surface area of the negative active material layer.
[0246] The above severability index may be 1 or less, or 0. If the above range is satisfied, the occurrence of battery short circuits, etc., can be suppressed, so the safety of the manufactured battery may be excellent and the lifespan characteristics may be excellent.
[0247] The above wrinkle index may be 1 or less, or 0. If the above range is satisfied, defects in the appearance of the battery can be suppressed, and lithium plating phenomena, destruction of the SEI film, etc. can be prevented, so that the safety and lifespan characteristics of the manufactured battery can be excellent.
[0249] Specifically, an electrode assembly can be formed including a cathode evaluated as good and an anode facing the cathode, and specifically, an electrode assembly can be formed by stacking the cathode evaluated as good, a separator, and an anode facing the cathode in order.
[0250] Types of electrode assemblies may include stack type, jelly roll type, stack and folding type, etc., but are not limited thereto.
[0252] Since the above-mentioned cathode is the same as previously described, a detailed explanation is omitted.
[0254] The anode may be manufactured by methods known in the art. For example, the anode may be manufactured by mixing an anode active material, an anode binder, and / or an anode conductive material in a solvent to prepare an anode slurry, applying the anode slurry onto an anode current collector, and then drying and rolling, or by casting the anode slurry onto a separate support and then laminating the film obtained by peeling it off from the support onto an anode current collector.
[0255] Meanwhile, solvents commonly used in the relevant technical field may be used as solvents for the anode slurry, for example, dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), acetone, water, or mixtures thereof, but are not limited thereto. The solvent may be used in an amount that dissolves or disperses the anode active material, anode conductive material, and anode binder, and has a viscosity such that the anode slurry can be uniformly coated.
[0256] The above positive electrode may include a positive current collector; and a positive active material layer; and the positive active material layer may include a positive active material.
[0257] Various positive current collectors used in the relevant technical field may be used as the positive current collector. For example, the positive current collector may be stainless steel, aluminum, nickel, titanium, calcined carbon, or aluminum or stainless steel surface treated with carbon, nickel, titanium, silver, etc. The positive current collector may typically have a thickness of 3 to 500 μm, and fine irregularities may be formed on the surface of the positive current collector to increase the adhesion of the positive active material. The positive current collector may be used in various forms, such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.
[0258] The positive active material layer may be located on the positive current collector, and specifically, may be located on one or both sides of the positive current collector. The positive active material layer may be a single layer or a multilayer structure of two or more layers.
[0259] The above-mentioned positive active material may be any positive active material commonly used in the relevant technical field, and its type is not particularly limited. The above-mentioned positive active material is a compound capable of reversible intercalation and deintercalation of lithium, and specifically, may include a lithium transition metal composite oxide comprising lithium and at least one transition metal composed of nickel, cobalt, manganese, and aluminum, preferably a lithium transition metal composite oxide comprising lithium and a transition metal comprising nickel, cobalt, and manganese.
[0260] More specifically, the lithium transition metal composite oxide is a lithium-manganese-based oxide (e.g., LiMnO2, LiMn2O4, etc.), a lithium-cobalt-based oxide (e.g., LiCoO2, etc.), a lithium-nickel-based oxide (e.g., LiNiO2, etc.), a lithium-nickel-manganese-based oxide (e.g., LiNi 1-Y Mn Y O2(here, 0 <Y<1), LiMn 2-z Niz O4 (where 0 < Z < 2), etc.), lithium-nickel-cobalt oxides (e.g., LiNi 1-Y1 Co Y1 O2(here, 0 <Y1<1) 등), 리튬-망간-코발트계 산화물(예를 들면, LiCo 1-Y2 Mn Y2 O2(here, 0 <Y2<1), LiMn 2-z1 Co z1 O4 (where 0 < Z1 < 2), etc.), lithium-nickel-manganese-cobalt oxides (e.g., Li(Ni p Co q Mn r1 )O2(where, 0<p<1, 0<q<1, 0<r1<1, p+q+r1=1) or Li(Ni p1 Co q1 Mn r2 )O4 (where 0<p1<2, 0<q1<2, 0<r2<2, p1+q1+r2=2) etc.), and lithium-nickel-cobalt-transition metal (M) oxide (e.g., Li(Ni p2 Co q2 Mn r3 M S2 It may include one or more selected from the group consisting of )O2 (wherein M is selected from the group consisting of Al, Fe, V, Cr, Ti, Ta, Mg, and Mo, and p2, q2, r3, and s2 are each atomic fractions of independent elements, such that 0 < p2 < 1, 0 < q2 < 1, 0 < r3 < 1, 0 < s2 < 1, p2 + q2 + r3 + s2 = 1), etc.). Among these, the lithium transition metal composite oxide may include LiCoO2, LiMnO2, LiNiO2, and lithium nickel-cobalt-manganese oxide (for example, Li(Ni 0.6 Mn 0.2 Co 0.2 )O2, Li(Ni 0.6 Mn 0.1 Co 0.3 )O2, Li(Ni 0.5 Mn 0.3 Co 0.2 )O2, Li(Ni0.7 Mn 0.15 Co 0.15 )O2 or Li(Ni 0.8 Mn 0.1 Co 0.1 )O2, etc.), and lithium nickel-cobalt-aluminum oxides (e.g., Li(Ni 0.8 Co 0.15 Al 0.05 It may include one or more selected from the group consisting of )O2, etc. Alternatively, considering the significant improvement effect resulting from controlling the type and content ratio of constituent elements forming the lithium transition metal composite oxide, the lithium transition metal composite oxide may be Li(Ni 0.6 Mn 0.2 Co 0.2 )O2, Li(Ni 0.6 Mn 0.1 Co 0.3 )O2, Li(Ni 0.5 Mn 0.3 Co 0.2 )O2, Li(Ni 0.7 Mn 0.15 Co 0.15 )O2 and Li(Ni 0.8 Mn 0.1 Co 0.1 It may include one or more types selected from the group consisting of )O2.
[0261] The above positive active material may be included in an amount of 80 to 99.9 weight%, 85 to 99 weight%, or 90 to 98 weight% based on the total weight of the positive active material layer. If the above range is satisfied, sufficient capacity characteristics can be achieved.
[0263] The above positive active material layer may further include a positive conductive material.
[0264] The above-mentioned positive electrode conductive material is used to impart conductivity to the electrode, and in the battery being constructed, it may be used without special limitations as long as it possesses electronic conductivity without causing chemical changes. Specific examples include graphite such as natural graphite or artificial graphite; carbon-based materials such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, carbon fiber, carbon nanotube; metal powder or metal fiber such as copper, nickel, aluminum, or silver; conductive whiskers such as zinc oxide or potassium titanate; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives, and one of these alone or a mixture of two or more may be used. The above-mentioned positive electrode conductive material may typically be included in an amount of 0.1 to 30 weight%, 0.5 to 20 weight%, 0.8 to 10 weight%, or 1 to 5 weight% based on the total weight of the positive electrode active material layer.
[0265] The above positive active material layer may further include a positive binder.
[0266] The above-mentioned anode binder serves to improve adhesion between anode material particles and adhesion between the anode material and the anode current collector. Specific examples include fluoropolymer-based binders comprising polyvinylidene fluoride (PVDF) or polytetrafluoroethylene (PTFE); rubber-based binders comprising styrene butadiene rubber (SBR), acrylonitrile-butadiene rubber, or styrene-isoprene rubber; cellulose-based binders comprising carboxyl methyl cellulose (CMC), starch, hydroxypropyl cellulose, or regenerated cellulose; polyalcohol-based binders comprising polyvinyl alcohol; polyolefin-based binders comprising polyethylene or polypropylene; polyimide-based binders; and polyester-based binders. Examples include silane-based binders, and one of these alone or a mixture of two or more may be used. The anode binder may be included in an amount of 0.1 to 30 weight%, 0.5 to 20 weight%, 0.8 to 10 weight%, or 1 to 5 weight% based on the total weight of the anode active material layer.
[0268] The separator may be interposed between the anode and the cathode. The separator separates the cathode and the anode and provides a pathway for the movement of lithium ions; any separator typically used as a separator in a lithium secondary battery may be used without any particular limitations. Specifically, the separator may be a porous polymer film, such as a porous polymer film made of a polyolefin-based polymer like ethylene homopolymer, propylene homopolymer, ethylene / butene copolymer, ethylene / hexene copolymer, and ethylene / methacrylate copolymer, or a laminated structure of two or more layers thereof. Alternatively, a conventional porous nonwoven fabric, such as a nonwoven fabric made of high-melting-point glass fiber or polyethylene terephthalate fiber, may be used. Furthermore, a coated separator containing ceramic components or polymer materials may be used to ensure heat resistance or mechanical strength.
[0270] Afterwards, the above electrode assembly can be housed inside a battery case, an electrolyte is injected, and the battery case is sealed to manufacture a lithium secondary battery.
[0271] The above sealing can be performed by heat welding or heat fusing the opened portion of the battery case.
[0273] The above battery case can serve to accommodate the electrode assembly and the electrolyte.
[0274] Specifically, the battery case is intended to house an electrode assembly, inject an electrolyte, and then seal it. It is manufactured from a material having a certain flexibility to form a housing portion, and while there are no limitations on its shape, it may preferably be cylindrical, coin-shaped, prismatic, or pouch-shaped. The upper case and lower case constituting the battery case may be independent members, or they may be substantially a single member with one end connected. The external shape of the battery case may be manufactured in various ways, and the present invention does not limit this.
[0275] For example, the battery case may be a pouch-type battery case. The pouch-type battery case may be manufactured by molding a pouch film laminate. The pouch-type battery case may accommodate the electrode assembly inside an outer material manufactured by molding a pouch film laminate.
[0276] The above pouch film laminate may have a substrate layer, a gas barrier layer, and a sealant layer laminated in sequence, but is not limited thereto.
[0277] Specifically, the substrate layer is formed on the outermost layer of the pouch film laminate to protect the secondary battery from friction and collision with the outside. The substrate layer is made of a polymer and can electrically insulate the electrode assembly from the outside.
[0278] The above substrate layer may be composed of one or more materials selected from the group consisting of polyethylene, polypropylene, polycarbonate, polyethylene terephthalate, polyvinyl chloride, acrylic polymer, polyacrylonitrile, polyimide, polyamide, cellulose, nylon, polyester, polyparaphenylenebenzobisoxazole, polyarylate, and Teflon. Among these, it is preferable that the substrate layer be composed of polyethylene terephthalate (PET), nylon, or a combination thereof, which possess wear resistance and heat resistance.
[0279] The above gas barrier layer is laminated between the substrate layer and the sealant layer to secure the mechanical strength of the pouch, block the entry and exit of gases or moisture from outside the secondary battery, and prevent electrolyte leakage from inside the pouch-type battery case. The above gas barrier layer may be formed of metal. For example, the above gas barrier layer may be a metal thin film comprising one or more metals selected from the group consisting of aluminum (Al), copper (Cu), stainless steel (SUS), nickel (Ni), titanium (Ti), and invar, but is not limited thereto.
[0280] The sealant layer is intended to completely seal the inside of a pouch-type battery case by mutually thermally bonding at the sealing portion when the pouch-type battery case, which accommodates an electrode assembly (270) on the inside, is sealed. To this end, the sealant layer may be formed of a material having excellent thermal bonding strength.
[0281] The sealant layer can be formed from a material having insulating, corrosion-resistant, and sealing properties. Specifically, since the sealant layer comes into direct contact with the electrode assembly (270) and / or electrolyte (not shown) inside the pouch-type battery case, it can be formed from a material having insulating and corrosion-resistant properties. Additionally, since the sealant layer must completely seal the inside of the pouch-type battery case to block material transfer between the inside and outside, it can be formed from a material having high sealing properties (e.g., excellent thermal sealing strength). To ensure these insulating, corrosion-resistant, and sealing properties, the sealant layer can be formed from a polymer material.
[0282] Specifically, the sealant layer may be composed of one or more materials selected from the group consisting of polyethylene, polypropylene, polycarbonate, polyethylene terephthalate, polyvinyl chloride, acrylic polymer, polyacrylonitrile, polyimide, polyamide, cellulose, nylon, polyester, polyparaphenylenebenzobisoxazole, polyarylate, and Teflon, and preferably may be composed of a polyolefin resin such as polypropylene (PP) and / or polyethylene (PE). In this case, the polypropylene may be composed of cast polypropylene (CPP), acid-modified polypropylene (PPA), polypropylene-ethylene copolymer, and / or polypropylene-butylene-ethylene terpolymer.
[0284] FIG. 2 is an exploded assembly diagram of a lithium secondary battery according to the present invention.
[0285] The pouch film laminate can be drawn and stretched by means of a punch or the like for the manufacture of a pouch-type battery case. As a result, referring to FIG. 1, the pouch-type battery case may include a cup portion (232) and a receiving portion (234). The receiving portion (234) is a place for receiving an electrode assembly (270), and may refer to a receiving space formed in the shape of a pocket inside the cup portion (232) as the cup portion (232) is formed. The receiving portion may correspond to an internal space of the battery case that receives the electrode assembly and the electrolyte.
[0286] Meanwhile, the pouch-type battery case may include a first case (230) and a second case (240). The first case (230) includes a receiving portion (234) capable of receiving an electrode assembly (270), and the second case (240) may cover the receiving portion (234) from above so that the electrode assembly (270) does not escape from the outside of the battery case. The first case (230) and the second case (240) may be manufactured with one side connected to the other, but are not limited thereto and may be manufactured in various ways, such as being separated from each other and manufactured separately.
[0288] According to another embodiment of the present invention, when forming cup portions (232, 242) in a pouch film laminate, two cup portions (232, 242) that are symmetrical to one pouch film laminate can be drawn and formed adjacent to each other. In this case, a cup portion (242) can be formed in each of the first case (230) and the second case (240). After receiving an electrode assembly (270) in a receiving portion (234) provided in the cup portion (232) of the first case (230), a bridge portion (250) formed between the two cup portions (232, 242) can be folded so that the two cup portions (242) face each other. In this case, the cup portion (242) of the second case (240) can receive the electrode assembly (270) from above. Therefore, since two cup portions (232, 242) accommodate one electrode assembly (270), an electrode assembly (270) with a thicker thickness than when there is only one cup portion can be accommodated. Additionally, since one corner of the secondary battery is formed by folding the pouch-type battery case, the number of corners to be sealed can be reduced when performing a sealing process later. Accordingly, the processing speed of the pouch-type secondary battery (200) can be improved and the number of sealing processes can be reduced.
[0289] A pouch-type battery case can be sealed while housing an electrode assembly (270) so that a part of the electrode lead (10), which will be described later, i.e., a terminal part, is exposed. Specifically, when the electrode lead (10) is connected to the electrode tab (280) of the electrode assembly (270) and a lead film (290) is attached to a part of the electrode lead (10), the electrode assembly (270) is housed in a housing portion (234) provided in the cup portion (232) of the first case (230), and the second case (240) can cover the housing portion (234) from above. Subsequently, an electrolyte (not shown) is injected into the interior of the housing portion (234), and a sealing portion (260) formed on the edges of the first case (230) and the second case (240) can be sealed.
[0290] The sealing portion (260) can perform the function of sealing the receiving portion (234). Specifically, the sealing portion (260) can seal the receiving portion (234) by being formed along the edge of the receiving portion (234). The temperature at which the sealing portion (260) is sealed may be 180°C to 250°C, specifically 200°C to 250°C, and more specifically 210°C to 240°C. When the sealing temperature satisfies the above numerical range, the pouch-type battery case can secure sufficient sealing strength by thermal bonding.
[0291] At this time, the sealing portion (260) can be formed by folding in the direction of the receiving portion (234) to secure the energy density of the lithium secondary battery.
[0294] The above electrolyte may include a lithium salt and an organic solvent.
[0295] The above lithium salt can be used without special limitations as long as it is a compound capable of providing lithium ions used in lithium secondary batteries. Specifically, the above lithium salt may include one or more selected from the group consisting of LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI, or LiB(C2O4)2, preferably LiPF6.
[0296] The concentration of the lithium salt may be 0.1 to 3.0 M, 0.1 to 2.0 M, or 0.5 to 1.5 M. When the concentration of the lithium salt falls within the above range, the electrolyte has appropriate conductivity and viscosity, so it can exhibit excellent electrolyte performance and lithium ions can move effectively.
[0298] The above organic solvent is a non-aqueous solvent commonly used in lithium secondary batteries, and is not particularly limited as long as it minimizes decomposition due to oxidation reactions, etc., during the charging and discharging process of the secondary battery.
[0299] Specifically, the organic solvent may include at least one selected from the group consisting of cyclic carbonate-based organic solvents, linear carbonate-based organic solvents, linear ester-based organic solvents, and cyclic ester-based organic solvents.
[0300] Specifically, the organic solvent may include a cyclic carbonate-based organic solvent, a linear carbonate-based organic solvent, or a mixture thereof.
[0301] The above-mentioned cyclic carbonate-based organic solvent is a high-viscosity organic solvent that has a high dielectric constant and can effectively dissociate lithium salts in the electrolyte; specifically, it may be a non-fluorinated saturated cyclic carbonate-based organic solvent. The above-mentioned cyclic carbonate-based organic solvent may include at least one organic solvent selected from the group consisting of ethylene carbonate (EC), fluoroethylene carbonate (FEC), propylene carbonate (PC), 1,2-butylene carbonate, 2,3-butylene carbonate, 1,2-pentylene carbonate, 2,3-pentylene carbonate, and vinylene carbonate; more specifically, it may include at least one selected from the group consisting of ethylene carbonate (EC) and fluoroethylene carbonate (FEC); and even more specifically, it may include ethylene carbonate (EC).
[0302] In addition, the linear carbonate-based organic solvent is an organic solvent having low viscosity and low dielectric constant, and specifically may be a non-fluorinated linear carbonate. The linear carbonate-based solvent may include at least one selected from the group consisting of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate, ethylmethyl carbonate (EMC), methylpropyl carbonate, and ethylpropyl carbonate; more specifically, it may include at least one selected from the group consisting of ethylmethyl carbonate (EMC) and diethyl carbonate (DEC); and more specifically, it may include ethylmethyl carbonate (EMC).
[0303] The above organic solvent may be a mixture of a cyclic carbonate-based organic solvent and a linear carbonate-based organic solvent. In this case, the cyclic carbonate-based organic solvent and the linear carbonate-based organic solvent may be mixed in a volume ratio of 5:95 to 40:60, or 10:90 to 38:62, or 25:75 to 35:65. When the mixing ratio of the cyclic carbonate-based organic solvent and the linear carbonate-based organic solvent satisfies the above range, high dielectric constant and low viscosity characteristics are simultaneously satisfied, and excellent ionic conductivity characteristics can be achieved.
[0304] In addition, to produce an electrolyte having high ionic conductivity, the organic solvent may further include at least one ester-based organic solvent selected from the group consisting of a linear ester-based organic solvent and a cyclic ester-based organic solvent in addition to at least one carbonate-based organic solvent selected from the group consisting of a cyclic carbonate-based organic solvent and a linear carbonate-based organic solvent.
[0305] The above linear ester-based organic solvent may specifically include at least one selected from the group consisting of methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, and butyl propionate.
[0306] In addition, the above-mentioned cyclic ester-based organic solvent may specifically include at least one selected from the group consisting of γ-butyrolactone, γ-valerolactone, γ-caprolactone, σ-valerolactone, and ε-caprolactone.
[0308] Meanwhile, the above organic solvent may be used without limitation by adding organic solvents commonly used in non-aqueous electrolytes as needed. For example, it may additionally include at least one organic solvent among ether-based organic solvents, glyme-based solvents, and nitrile-based organic solvents.
[0309] As the above ether-based solvent, any one selected from the group consisting of dimethyl ether, diethyl ether, dipropyl ether, methyl ethyl ether, methylpropyl ether, ethyl propyl ether, 1,3-dioxolane (DOL), and 2,2-bis(trifluoromethyl)-1,3-dioxolane (TFDOL), or a mixture of two or more of these may be used, but is not limited thereto.
[0310] The above-mentioned glyme-based solvent has a high dielectric constant and low surface tension compared to linear carbonate-based organic solvents and is a solvent with low reactivity with metals. It may include at least one selected from the group consisting of dimethoxyethane (glyme, DME), diethoxyethane, diglyme, triglyme, and tetraglyme (TEGDME), but is not limited thereto.
[0311] The above nitrile-based solvent may be one or more selected from the group consisting of acetonitrile, propionitrile, butyronitrile, valeronitrile, caprylonitrile, heptanitrile, cyclopentane carbonitrile, cyclohexane carbonitrile, 2-fluorobenzonitrile, 4-fluorobenzonitrile, difluorobenzonitrile, trifluorobenzonitrile, phenylacetonitrile, 2-fluorophenylacetonitrile, and 4-fluorophenylacetonitrile, but is not limited thereto.
[0313] Meanwhile, in addition to the electrolyte components, the above electrolyte may additionally include additives for the purpose of improving the lifespan characteristics of the battery, suppressing the reduction of battery capacity, and improving the discharge capacity of the battery.
[0314] The above additive may include, for example, at least one additive selected from the group consisting of non-fluorinated unsaturated cyclic carbonate compounds, halogen-substituted carbonate compounds, sulfone compounds, sulfate compounds, borate compounds, nitrile compounds, benzene compounds, amine compounds, silane compounds, and lithium salt compounds different from the lithium salt included in the electrolyte.
[0315] Specifically, the additive is vinylene carbonate (VC), vinylethylene carbonate, fluoroethylene carbonate (FEC), 1,3-propane sulfone (PS), 1,4-butane sulfone, ethene sulfone, 1,3-propene sulfone (PRS), 1,4-butene sulfone, 1-methyl-1,3-propene sulfone, ethylene sulfate (ESA), trimethylene sulfate (TMS), methyl trimethylene sulfate (MTMS), tetraphenyl borate, lithium oxalyl difluoroborate, succinonitrile, adiponitrile, acetonitrile, propionitrile, butyronitrile, valeronitrile, caprylonitrile, heptanitrile, cyclopentane carbonitrile, cyclohexane carbonitrile, 2-fluorobenzonitrile, Examples include one or more compounds selected from the group consisting of 4-fluorobenzonitrile, difluorobenzonitrile, trifluorobenzonitrile, phenylacetonitrile, 2-fluorophenylacetonitrile, 4-fluorophenylacetonitrile, fluorobenzene, triethanolamine, ethylenediamine, tetravinylsilane, LiN(SO2F)2 (Lithium bis(fluorosulfonyl)imide, LiFSI), LiN(SO2CF3)2 (lithium bis(trifluoromethane sulfonyl)imide, LiTFSI), LiPO2F2, LiODFB, LiBOB (lithium bis-oxalate toborate (LiB(C2O4)2)) and LiBF4.
[0316] The above additives may be included in an amount of 0.01 to 20 weight% based on the total weight of the electrolyte, or in an amount of 0.05 to 5.0 weight%. If the above range is satisfied, the lifespan characteristics and safety of the battery can be improved, side reactions in the electrolyte can be reduced, and the presence of the additives as unreacted substances can be suppressed.
[0318] A lithium secondary battery manufactured according to the method for manufacturing a lithium secondary battery according to the present invention is useful in portable devices such as mobile phones, laptop computers, and digital cameras, and in the field of electric vehicles such as hybrid electric vehicles (HEVs).
[0319] In addition, a battery module or battery pack including the above-mentioned lithium secondary battery as a unit cell can be used as a power source for one or more medium-to-large devices, including a power tool; an electric vehicle (EV), a hybrid electric vehicle, and a plug-in hybrid electric vehicle (PHEV); or a power storage system.
[0320] A lithium secondary battery manufactured according to the method for manufacturing a lithium secondary battery according to the present invention can be used not only as a battery cell used as a power source for a small device, but can also preferably be used as a unit cell in a medium-to-large battery module comprising a plurality of battery cells.
[0321] Examples of the above-mentioned medium-to-large devices include electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, and power storage systems, but are not limited to these.
[0323] cathode
[0324] The cathode according to the present invention comprises: a cathode current collector; and a cathode active material layer located on the cathode current collector and comprising a silicon-based cathode active material, wherein the adhesion index value defined by Formula 1 below is 4.0 gf or higher.
[0325] [Equation 1]
[0326] Adhesion index (unit: gf) = F2 - F1
[0327] In the above Equation 1, F1 (unit: gf) is the adhesion force between the negative current collector and the negative active material layer, and F2 (unit: gf) is the adhesion force between the negative current collector and the negative active material layer after immersing the negative electrode in liquid nitrogen.
[0329] Silicon-based anode active materials possess a significantly higher theoretical capacity compared to conventionally used graphite, offering the advantage of enabling high-capacity characteristics when utilized as anode active materials. However, silicon-based anode active materials exhibit a very large degree of volume change during the charge-discharge process; if charging and discharging continue, internal stress can accumulate in the anode, potentially causing wrinkling or delamination. Therefore, for anodes containing silicon-based active materials, it is crucial to design the anode to prevent wrinkling and / or delamination during charging and discharging.
[0330] Conventionally, in order to develop a cathode that does not develop wrinkles or / or delamination during charging and discharging, a cathode containing a silicon-based cathode active material was designed, a half-cell or full-cell was manufactured using the cathode, and charging and discharging were performed to check for the occurrence of wrinkles or / or delamination. Since the degree of volume expansion of silicon-based cathode active materials varies depending on their type and content, the cathode must be redesigned accordingly. However, the conventional method has the disadvantage of being inefficient in terms of time and cost because, since the occurrence of wrinkles or / or delamination cannot be predicted at the time of cathode design, a cell containing the cathode must be fabricated every time a cathode is designed to check for such occurrence.
[0331] Accordingly, the cathode according to the present invention includes a silicon-based cathode active material, and by designing the cathode such that the adhesion index value defined by Formula 1 satisfies a specific range, it is possible to manufacture a cathode that does not develop wrinkles and / or detachment during charging and discharging without separately manufacturing a cell containing the cathode each time to evaluate whether wrinkles and / or detachment occur.
[0333] Hereinafter, the cathode according to the present invention will be described in detail.
[0335] The cathode according to the present invention has an adhesion index value of 4.0 gf or higher, defined by the following formula 1.
[0336] The difference in adhesion between the cathode current collector and the cathode active material layer, measured before and after immersing the cathode in liquid nitrogen, can induce internal stress between the cathode current collector and the cathode active material layer due to the difference in the coefficient of thermal expansion. Since this can simulate the stress generated during charging and discharging, the adhesion index can serve as a parameter representing whether wrinkling and / or delamination of the cathode occur during charging and discharging of a lithium secondary battery containing the cathode. The value of the adhesion index can be adjusted to satisfy the above range by organically controlling the type and content of the cathode binder, the type and content of the cathode conductive material, the loading amount, thickness, and porosity of the cathode active material layer, the type and thickness of the cathode current collector, and the type and content of the cathode additive, depending on the type and content of the silicon-based cathode active material.
[0337] [Equation 1]
[0338] Adhesion index (unit: gf) = F2 - F1
[0339] In the above Equation 1, F1 (unit: gf) is the adhesion force between the negative current collector and the negative active material layer, and F2 (unit: gf) is the adhesion force between the negative current collector and the negative active material layer after immersing the negative electrode in liquid nitrogen.
[0340] The cathode according to the present invention has an adhesion index value defined by Formula 1 below of 4.0gf or higher, 4.2gf or higher, 4.4gf or higher, 4.6gf or higher, 4.8gf or higher, or 5.0gf or higher. When the above range is satisfied, wrinkles and / or delamination occurring on the cathode during charging and discharging of a lithium secondary battery manufactured using the cathode can be suppressed, and accordingly, the safety and lifespan characteristics of the lithium secondary battery can be improved.
[0341] The above F1 can be measured by forming a sample by punching the cathode into 20 mm × 125 mm and adhering it to a slide glass with double-sided tape attached, with the cathode surface attached, loading the sample into a UTM, positioning the jig and the sample at a 90° angle, and measuring the average value of the flat section of the stress-strain curve. Preferably, the above F1 can be measured by the above method immediately after manufacturing the cathode, or after disassembling a lithium secondary battery containing the cathode to separate the cathode.
[0342] The above F1 is It may be 20 to 65 gf, 25 to 60 gf, 30 to 55 gf, 40 to 52 gf, 45 to 50 gf, or 47 to 49 gf. If the above range is satisfied, it is possible to suppress wrinkling and detachment of the cathode that may occur when the adhesive strength is excessively high or low.
[0343] The above F2 can be measured by immersing the cathode in liquid nitrogen, then punching the cathode into a 20mm × 125mm shape, and attaching the cathode side to a slide glass with double-sided tape to produce a sample, loading the sample into a UTM, positioning the jig and the sample at a 90° angle, and measuring the average value of the flat section of the stress-strain curve. Preferably, the above F2 can be measured by the above method after immersing the cathode in liquid nitrogen, recovering the cathode from the liquid nitrogen, and drying it. More preferably, the above F2 can be measured by the above method after immersing the cathode in liquid nitrogen at -196°C for 10 minutes, then recovering the cathode from the liquid nitrogen, drying it, and recovering the cathode from the liquid nitrogen.
[0344] The above F2 is It may be 25 to 69 gf, 30 to 65 gf, 35 to 62 gf, 40 to 60 gf, 45 to 58 gf, or 50 to 56 gf. When the above range is satisfied, the adhesion between the negative current collector and the negative active material layer is adequately secured even during volume expansion and contraction of the silicon-based negative active material, thereby preventing detachment and wrinkling.
[0346] As the above-mentioned cathode current collector, cathode current collectors generally used in the relevant technical field may be used, for example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, etc., and aluminum-cadmium alloy may be used. The above-mentioned cathode current collector may typically have a thickness of 3 μm to 500 μm, and fine irregularities may be formed on the surface of the above-mentioned cathode current collector to strengthen the bonding strength of the cathode active material. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.
[0348] The above-mentioned negative electrode active material layer is located on the negative electrode current collector. Specifically, the negative electrode active material layer may be located on one or both sides of the negative electrode current collector and may be composed of a single layer or multiple layers.
[0349] The above-mentioned negative electrode active material layer includes a silicon-based negative electrode active material.
[0350] The above silicon-based negative electrode active material is silicon (Si) and silicon oxide (SiO₂). x (0 <x<2)로 표시될 수 있음) 및 Si / C 복합체(Si / C Composite)로 이루어진 군에서 선택된 적어도 1종을 포함할 수 있고, 바람직하게는 Si / C 복합체를 포함할 수 있다.
[0351] The silicon-based negative electrode active material may be included in an amount of 5 to 15 weight%, 7 to 13 weight%, or 8 to 12 weight% based on the total weight of the negative electrode active material layer. When the above range is satisfied, the capacity characteristics, rapid charging characteristics, and lifespan characteristics may all be excellent.
[0353] The above-mentioned negative electrode active material layer may further include other negative electrode active materials in addition to the silicon-based negative electrode active material.
[0354] The above other negative electrode active material may be a compound capable of reversible intercalation and deintercalation of lithium in addition to a silicon-based negative electrode active material, and may be, for example, one or more selected from the group consisting of a carbon-based negative electrode active material, a metallic compound capable of alloying with lithium, and a metal oxide capable of doping and dedoping lithium. Specifically, the above carbon-based negative electrode active material may be one or more selected from the group consisting of artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon, or one or more selected from the group consisting of artificial graphite and natural graphite. The above metallic compound may be one or more selected from the group consisting of Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloy, Sn alloy, and Al alloy. The above metal oxide may be one or more selected from the group consisting of SnO2, vanadium oxide, and lithium vanadium oxide.
[0355] Preferably, the other negative electrode active material may be a carbon-based negative electrode active material.
[0356] The above other cathode active material may be included in an amount of 85 to 95 weight%, 87 to 93 weight%, or 88 to 92 weight% based on the total weight of the cathode active material layer. When the above range is satisfied, the lifespan characteristics may be excellent.
[0358] The above cathode active material layer may further include a cathode conductive material.
[0359] A cathode conductive material is used to impart conductivity to the cathode, and in a battery being constructed, any material that possesses electronic conductivity without causing chemical changes can be used without any special limitations. Specifically, the cathode conductive material may include carbon-based materials such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, carbon fiber, carbon nanotube; metal powders or metal fibers such as copper, nickel, aluminum, or silver; conductive whiskers such as zinc oxide or potassium titanate; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives, and one of these alone or a mixture of two or more may be used.
[0360] The above-mentioned cathode conductive material may typically be included in an amount of 0.1 to 10 weight%, 0.1 to 8 weight%, or 0.1 to 5 weight% based on the total weight of the cathode active material layer. When the above range is satisfied, the energy density can be excellent while sufficiently ensuring conductivity within the cathode active material layer.
[0361] The above cathode active material layer may further include a cathode binder.
[0362] The above-mentioned cathode binder serves to improve adhesion between cathode active material particles and adhesion between the cathode active material and the cathode current collector. Specifically, the above-mentioned cathode binder may include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer rubber (EPDM rubber), sulfonated-EPDM, styrene-butadiene rubber (SBR), fluororubber, acrylic acid, polyacrylamide, or various copolymers thereof, and one of these alone or a mixture of two or more may be used.
[0363] More specifically, the cathode binder may include an elastomer binder and an acrylic binder. In this case, it may be effective in suppressing the occurrence of wrinkling and delamination during charging and discharging while appropriately improving the adhesion between the cathode active material layer and the cathode current collector.
[0364] The above rubber-based binder may be one or more selected from the group consisting of styrene-butadiene rubber, sulfonated-EPDM, ethylene-propylene-diene monomer rubber (EPDM rubber), and fluororubber, or it may be styrene-butadiene rubber. By controlling the particle size and surface functional groups of the above rubber-based binder, the adhesion index defined by Formula 1 may satisfy the desired range.
[0365] The above acrylic binder may be one or more selected from the group consisting of polyacrylonitrile, acrylic acid, polyacrylamide, and copolymers thereof, or may be a copolymer of polyacrylonitrile, acrylic acid, and polyacrylamide. When the above acrylic binder is a copolymer of polyacrylonitrile, acrylic acid, and polyacrylamide, the molar ratio between polyacrylonitrile, acrylic acid, and polyacrylamide can be appropriately adjusted so that the adhesion strength index satisfies the desired range.
[0366] The rubber-based binder and the acrylic-based binder may be included in a weight ratio of 4:6 to 6:4, 4.2:5.8 to 5.8:4.2, or 4.5:5.5 to 5.5:4.5. When the above ranges are satisfied, the adhesion strength index may satisfy the desired range, and delamination and wrinkling occurring at the negative electrode during charging and discharging may be suppressed.
[0367] The above-mentioned cathode binder may be included in an amount of 0.1 to 10 weight%, 0.5 to 10 weight%, 1 to 5 weight%, or 2 to 4 weight% based on the total weight of the cathode active material layer. When the above range is satisfied, the adhesion with the cathode current collector is adequately secured, and the energy density can be excellent.
[0368] The above cathode active material layer may further include a cathode additive. The above cathode additive may contribute to controlling the adhesion index defined by Equation 1.
[0369] The above cathode additive may include carboxymethyl cellulose. In this case, viscosity is imparted to the cathode active material layer to improve adhesion between cathode active material particles and between the cathode active material layer and the cathode current collector, and the dispersibility of the cathode active material layer can be increased.
[0370] The above cathode additive may be included in an amount of 0.1 to 2 weight%, 0.2 to 1 weight%, or 0.3 to 0.7 weight% based on the total weight of the cathode active material layer. When the above range is satisfied, the adhesion index defined by Formula 1 can be controlled, and the additive can sufficiently perform its role while improving energy density.
[0372] The above cathode active material layer has a loading amount of 100 mg / 25 cm 2 Up to 400 mg / 25 cm 2 , 125mg / 25cm 2 Up to 300 mg / 25 cm 2 , 150mg / 25cm 2 Up to 250 mg / 25 cm 2 , or 180mg / 25cm 2 Up to 220 mg / 25 cm 2 It may be possible. If the above range is satisfied, the energy density is excellent, and the stress on the cathode can be relieved as the cathode active material layer expands in volume during charging and discharging.
[0374] The above-mentioned negative electrode active material layer may have a thickness of 30 to 100 μm, 40 to 90 μm, or 45 to 85 μm. When the above range is satisfied, sufficient capacitance characteristics can be achieved, and the stress on the negative electrode can be relieved as the negative electrode active material layer expands in volume during charging and discharging.
[0376] The above-mentioned negative electrode active material layer may have a porosity of 10 to 40%, 20 to 35%, or 22 to 32%. When the above ranges are satisfied, the energy density is excellent, and the stress on the negative electrode can be relieved as the negative electrode active material layer expands in volume during charging and discharging.
[0378] The above cathode may have a risk level defined by the following formula A that is 2 or less, 1 or less, or 0. If the above range is satisfied, the safety and lifespan characteristics of the cathode may be excellent.
[0379] [Equation A]
[0380] Risk Level = Talley Index + Wrinkle Index
[0381] In the above Equation A, the delamination index and the wrinkle index are measured by separating the negative electrode after charging the lithium secondary battery comprising the negative electrode, positive electrode, and electrolyte to 100% SOC, wherein the delamination index is 3 if delamination occurs in 50% or more of the interface area between the negative electrode active material layer and the negative electrode current collector, 2 if delamination occurs in 10% to 50% of the interface area between the negative electrode active material layer and the negative electrode current collector, 1 if delamination occurs in 0.1% to 10% of the interface area between the negative electrode active material layer and the negative electrode current collector, and 0 if delamination occurs in 0.1% or less of the interface area between the negative electrode active material layer and the negative electrode current collector; and the wrinkle index is 3 if wrinkles occur in 50% or more of the surface area of the negative electrode active material layer, 2 if wrinkles occur in 10% to 50% of the surface area of the negative electrode active material layer, and the surface area of the negative electrode active material layer If wrinkles occur in 0.1% to 10%, it is 1, and if wrinkles occur in 0.1% or less of the surface area of the negative electrode active material layer, it is 0.
[0382] The above severability index may be 1 or less, or 0. If the above range is satisfied, the occurrence of battery short circuits, etc., can be suppressed, so the safety of the battery can be excellent and the lifespan characteristics can be excellent.
[0383] The above wrinkle index may be 1 or less, or 0. If the above range is satisfied, defects in the appearance of the battery can be suppressed, and lithium plating phenomena, destruction of the SEI film, etc. can be prevented, so that the safety and lifespan characteristics of the battery can be excellent.
[0385] lithium secondary battery
[0386] A lithium secondary battery according to the present invention comprises a negative electrode according to the present invention, a positive electrode opposed thereto, and an electrolyte. By using a negative electrode in which wrinkling and / or delamination is suppressed during charging and discharging, the lithium secondary battery according to the present invention may have excellent safety and lifespan characteristics.
[0388] Since the above-mentioned cathode is the same as that described above in the cathode according to the present invention, a detailed description is omitted.
[0390] Since the above-mentioned positive electrode is the same as that described above in the method for manufacturing a lithium secondary battery according to the present invention, a detailed description is omitted.
[0392] Since the above electrolyte is the same as that described above in the method for manufacturing a lithium secondary battery according to the present invention, a detailed description is omitted.
[0394] The above lithium secondary battery may further include a separator.
[0395] Since the above-mentioned separator is the same as that described above in the method for manufacturing a lithium secondary battery according to the present invention, a detailed description is omitted.
[0397] Specifically, the lithium secondary battery may include an electrode assembly comprising a negative electrode and a positive electrode opposite to the negative electrode; an electrolyte; and a battery case.
[0398] The electrode assembly may include the cathode and the anode facing the cathode, or may include the cathode, the separator, and the anode facing the cathode stacked in sequence. Types of the electrode assembly may include, but are not limited to, stack type, jelly roll type, stack and folding type, etc.
[0399] The above electrolyte is the same as previously described, so a detailed explanation is omitted.
[0401] The battery case described above may serve to accommodate the electrode assembly and the electrolyte. Specifically, the battery case is intended to house the electrode assembly, inject the electrolyte, and then seal it. It is manufactured from a material having a certain flexibility to form a housing portion, and while there are no limitations on its shape, it may preferably be cylindrical, coin-shaped, prismatic, or pouch-shaped. The upper case and lower case constituting such a battery case may be independent members, or they may be substantially a single member with one end connected. The external shape of the battery case may be manufactured in various ways, and the present invention does not limit this.
[0402] For example, the battery case may be a pouch-type battery case. Since the pouch-type battery case is the same as that described above in the method for manufacturing a lithium secondary battery according to the present invention, a detailed description is omitted.
[0404] The present invention will be explained in more detail below through specific embodiments. However, the following embodiments are intended only to enable a person skilled in the art to fully understand and easily implement the present invention, and the scope of the present invention is not limited to the following embodiments.
[0406] Reference Example
[0407] A cathode active material layer slurry was prepared by mixing synthetic graphite as the cathode active material, carbon black as the cathode conductive material, styrene butadiene rubber A as the cathode binder, and carboxymethylcellulose as the cathode additive in distilled water at a weight ratio of 95.8:0.5:2.5:1.2. (Viscosity: 5360 cP)
[0408] 276 mg / 25 cm of the above negative electrode active material layer slurry is applied to one surface of a copper current collector with a thickness of 15 μm. 2 An electrode was manufactured by applying a loading amount, drying, and forming a negative active material layer with a thickness of 70 μm.
[0410] Preparation Example 1
[0411] A cathode active material layer slurry was prepared by mixing a Si / C composite as a silicon-based cathode active material, artificial graphite as an other cathode active material, carbon black as a cathode conductive material, styrene butadiene rubber B and acrylic binder A as cathode binders, and carboxymethylcellulose as a cathode additive in distilled water at a weight ratio of 9.6:86.3:0.5:1.5:1.6:0.5. (Viscosity: 7560 cP)
[0412] 200 mg / 25 cm of the above negative electrode active material layer slurry is applied to one surface of a copper current collector with a thickness of 15 μm. 2 An electrode was manufactured by applying a loading amount, drying, and forming a negative active material layer with a thickness of 53 μm.
[0414] Preparation Example 2
[0415] A cathode active material layer slurry was prepared by mixing a Si / C composite as a silicon-based cathode active material, artificial graphite as an other cathode active material, carbon black as a cathode conductive material, and styrene butadiene rubber B and acrylic binder A as cathode binders in distilled water at a weight ratio of 9.6:8:6.3:0.5:1.8:1.8. (Viscosity: 6410 cP)
[0416] 200 mg / 25 cm of the above negative electrode active material layer slurry is applied to one surface of a copper current collector with a thickness of 15 μm. 2 An electrode was manufactured by applying a loading amount, drying, and forming a negative active material layer with a thickness of 53 μm.
[0418] Preparation Example 3
[0419] A cathode active material layer slurry was prepared by mixing a Si / C composite as a silicon-based cathode active material, artificial graphite as an other cathode active material, carbon black as a cathode conductive material, styrene butadiene rubber B and acrylic binder B as cathode binders, and carboxymethylcellulose as a cathode additive in distilled water at a weight ratio of 9.6:86.3:0.5:1.5:1.6:0.5. (Viscosity: 2890 cP)
[0420] 200 mg / 25 cm of the above negative electrode active material layer slurry is applied to one surface of a copper current collector with a thickness of 15 μm. 2 An electrode was manufactured by applying a loading amount, drying, and forming a negative active material layer with a thickness of 52 μm.
[0422] Preparation Example 4
[0423] A cathode active material layer slurry was prepared by mixing a Si / C composite as a silicon-based cathode active material, artificial graphite as an other cathode active material, carbon black as a cathode conductive material, and styrene butadiene rubber C and acrylic binder C as cathode binders in distilled water at a weight ratio of 9.6:8:6.3:0.5:0.9:2.7. (Viscosity: 7500 cP)
[0424] 200 mg / 25 cm of the above negative electrode active material layer slurry is applied to one surface of a copper current collector with a thickness of 15 μm. 2 An electrode was manufactured by applying a loading amount, drying, and forming a negative active material layer with a thickness of 54 μm.
[0426] Preparation Example 5
[0427] A cathode active material layer slurry was prepared by mixing a Si / C composite as a silicon-based cathode active material, artificial graphite as an other cathode active material, carbon black as a cathode conductive material, and styrene butadiene rubber D and acrylic binder C as cathode binders in distilled water at a weight ratio of 9.6:8:6.3:0.5:0.9:2.7. (Viscosity: 3740 cP)
[0428] 200 mg / 25 cm of the above negative electrode active material layer slurry is applied to one surface of a copper current collector with a thickness of 15 μm. 2 An electrode was manufactured by applying a loading amount, drying, and forming a negative active material layer with a thickness of 55 μm.
[0430] Preparation Example 6
[0431] A cathode active material layer slurry was prepared by mixing a Si / C composite as a silicon-based cathode active material, artificial graphite as an other cathode active material, carbon black as a cathode conductive material, and styrene butadiene rubber B and acrylic binder C as cathode binders in distilled water at a weight ratio of 9.6:8:6.3:0.5:1.8:1.8. (Viscosity: 2930 cP)
[0432] 200 mg / 25 cm of the above negative electrode active material layer slurry is applied to one surface of a copper current collector with a thickness of 15 μm. 2 An electrode was manufactured by applying a loading amount, drying, and forming a negative active material layer with a thickness of 50 μm.
[0434] Preparation Example 7
[0435] A cathode active material layer slurry was prepared by mixing a Si / C composite as a silicon-based cathode active material, artificial graphite as an other cathode active material, carbon black as a cathode conductive material, and styrene butadiene rubber B and acrylic binder C as cathode binders in distilled water at a weight ratio of 9.6:8:6.3:0.5:0.9:2.7. (Viscosity: 6210 cP)
[0436] 200 mg / 25 cm of the above negative electrode active material layer slurry is applied to one surface of a copper current collector with a thickness of 15 μm. 2 An electrode was manufactured by applying a loading amount, drying, and forming a negative active material layer with a thickness of 50 μm.
[0438] Preparation Example 8
[0439] A cathode active material layer slurry was prepared by mixing a Si / C composite as a silicon-based cathode active material, artificial graphite as an other cathode active material, carbon black as a cathode conductive material, and acrylic binder D as a cathode binder in distilled water at a weight ratio of 9.6:86.9:0.5:3.0. (Viscosity: 6610 cP)
[0440] 200 mg / 25 cm of the above negative electrode active material layer slurry is applied to one surface of a copper current collector with a thickness of 15 μm. 2An electrode was manufactured by applying a loading amount, drying, and forming a negative active material layer with a thickness of 53 μm.
[0442] Preparation Example 9
[0443] A cathode active material layer slurry was prepared by mixing a Si / C composite as a silicon-based cathode active material, artificial graphite as an other cathode active material, carbon black as a cathode conductive material, and acrylic binder E as a cathode binder in distilled water at a weight ratio of 9.6:86.9:0.5:3.0. (Viscosity: 3920 cP)
[0444] 200 mg / 25 cm of the above negative electrode active material layer slurry is applied to one surface of a copper current collector with a thickness of 15 μm. 2 An electrode was manufactured by applying a loading amount, drying, and forming a negative active material layer with a thickness of 54 μm.
[0446] In the above reference examples and preparation examples 1 to 9, acrylic binders A to E are polyacrylamide-acrylic acid-acrylonitrile copolymers, and the molar ratios of polyacrylamide, acrylic acid, and acrylonitrile were each controlled, and the particle size and surface functional groups of styrene butadiene rubbers A to D were each controlled.
[0448] Experimental Example 1: Evaluation of Cathode Quality
[0449] The quality of the cathodes of the above Reference Example and Manufacturing Examples 1 to 9 was evaluated by setting the reference value derived from the database to 5gf. The results are shown in Table 1 below.
[0451] Specifically, the adhesion index defined by the following Formula 1 of the above Reference Example and Manufacturing Examples 1 to 9 was measured.
[0452] [Equation 1]
[0453] Adhesion index (unit: gf) = F2 - F1
[0454] In the above Equation 1, F1 (unit: gf) is the adhesion force between the cathode current collector and the cathode active material layer, and F2 (unit: gf) is the adhesion force between the cathode current collector and the cathode active material layer after immersing the cathode in liquid nitrogen, and was measured by the following method.
[0455] The above F1 was measured by punching the cathodes of the above reference examples and manufacturing examples 1 to 9 into 20 mm × 125 mm, attaching them to a slide glass with double-sided tape with the cathode surface, and then loading the sample into a UTM and positioning the jig and the sample at a 90° angle, and measuring the average value of the flat section of the stress-strain curve.
[0456] The above F2 was prepared by immersing the cathodes of the above Reference Example and Preparation Examples 1 to 9 in liquid nitrogen at -196°C for 10 minutes, recovering them, punching out the cathodes after immersion into 20 mm × 125 mm, and attaching the cathode surface to a slide glass with double-sided tape attached, then loading the sample into a UTM, positioning the jig and the sample at a 90° angle, and measuring the average value of the flat section of the stress-strain curve.
[0458] F1[gf] F2[gf] Adhesion index [gf] Good quality Reference Example 21 27.7 6.7 fair quality Preparation Example 1 48.2 53.2 5 fair quality Preparation Example 2 65.9 69.9 3.7 error Preparation Example 3 18.4 19.8 1.4 error Preparation Example 4 24.6 22.3 -2.3 error Preparation Example 5 27 24.1 -2.9 error Preparation Example 6 23.6 19.3 -4.3 error Preparation Example 7 25.6 15.6 -10 error Preparation Example 8 33.5 34.5 1.0 error Preparation Example 9 23.6 23.0 -0.6 error
[0459] Referring to Table 1 above, Manufacturing Example 1 and Reference Example were evaluated as good products because their adhesion index was 5gf or higher, and Manufacturing Examples 2 to 9 were evaluated as defective because their adhesion index was less than 5gf.
[0460] Experimental Example 2: Risk Level Assessment
[0461] An electrode assembly was manufactured by interposing a separator between the negative electrode and the positive electrode prepared in the above reference examples and manufacturing examples 1 to 9, and then the assembly was placed inside a pouch-type battery case, and then an electrolyte was injected into the pouch-type battery case to manufacture a lithium secondary battery.
[0462] The above anode was manufactured by preparing an anode slurry by mixing LiCoO2 as the anode active material, carbon black as the conductive material, and polyvinylidene fluoride (PVDF) as the binder in a weight ratio of 97.6:1.1:1.3 in an N-methylpyrrolidone solvent, applying the anode slurry onto an aluminum current collector, drying it, and then rolling it.
[0463] The above electrolyte was prepared by dissolving 1.2 M LiPF6 in an organic solvent mixed with ethylene carbonate (EC):polycarbonate (PC):ethylpropionate (EP):polypropylene (PP) in a volume ratio of 20:10:25:45.
[0464] The lithium secondary battery manufactured above was charged to SOC 100% (0.05C cut-off) at 25℃ with CC / CV and a 0.2C-rate.
[0466] Subsequently, the above lithium secondary battery was disassembled, and the degree of wrinkling and delamination of the negative electrode was visually inspected to evaluate the risk level of the negative electrode defined by the following formula A. The results are shown in Table 2 below, and images of the negative electrodes of Reference Example and Manufacturing Examples 1 to 9 are shown in FIGS. 3 to 12.
[0467] [Equation A]
[0468] Risk Level = Talley Index + Wrinkle Index
[0469] In the above formula A, the delamination index is 3 if delamination occurs in 50% or more of the interface area between the negative electrode active material layer and the negative electrode current collector, 2 if delamination occurs in 10% to 50% of the interface area between the negative electrode active material layer and the negative electrode current collector, 1 if delamination occurs in 0.1% to 10% of the interface area between the negative electrode active material layer and the negative electrode current collector, and 0 if delamination occurs in 0.1% or less of the interface area between the negative electrode active material layer and the negative electrode current collector; and the wrinkle index is 3 if wrinkles occur in 50% or more of the surface area of the negative electrode active material layer, 2 if wrinkles occur in 10% to 50% of the surface area of the negative electrode active material layer, 1 if wrinkles occur in 0.1% to 10% of the surface area of the negative electrode active material layer, and 0 if wrinkles occur in 0.1% or less of the surface area of the negative electrode active material layer.
[0470] Wrinkle index Tali Index Risk level Reference Example 0 0 0 Preparation Example 1 1 0 1 Preparation Example 2 2 1 3 Preparation Example 3 3 1 4 Preparation Example 4 2 2 4 Preparation Example 5 3 3 6 Preparation Example 6 3 2 5 Preparation Example 7 3 3 6 Preparation Example 8 2 1 3 Preparation Example 9 1 3 4
[0471] Referring to Table 2 and Figures 3 and 4 above, it can be seen that the risk level of the negative electrode measured after charging and discharging the lithium secondary battery manufactured using Reference Example and Manufacturing Example 1, which were evaluated as good products, is very low at a level of 1 or less. On the other hand, referring to Table 2 and Figures 5 to 12 above, it can be seen that the risk level of the negative electrode measured after charging and discharging the lithium secondary battery manufactured using Manufacturing Examples 2 to 9, which were evaluated as defective products, is high at less than 1. Explanation of the symbols
[0473] 10: Electrode Lead 20: Positive lead 30: Cathode lead 230: First case 232: Cups 234: Reception Department 240: Second case 242: Cups 250: Bridge section 260: Sealing part 270: Electrode assembly 280: Electrode tab 282: Positive tab 284: Cathode tab 290: Lead film
Claims
Claim 1 A method for evaluating the quality of a cathode, comprising: a step (S1) of preparing a cathode including a cathode current collector and a cathode active material layer located on the cathode current collector and including a silicon-based cathode active material; a step (S2) of measuring an adhesion force F1 between the cathode current collector and the cathode active material layer; a step (S3) of immersing the cathode in liquid nitrogen and then measuring an adhesion force F2 between the cathode current collector and the cathode active material layer; and a step (S4) of evaluating the quality of the cathode by evaluating it as a good product if the adhesion force index value defined by the following Equation 1 is greater than or equal to a reference value, and as a defective product if it is less than the reference value. [Equation 1] Adhesion force index (unit: gf) = F2 (unit: gf) - F1 (unit: gf) Claim 2 A method for evaluating the quality of a cathode according to claim 1, wherein the good product is a cathode having a risk level defined by the following formula A of 2 or less. [Formula A] Risk level = Delamination index + Wrinkle index. In the above formula A, the delamination index and the wrinkle index are measured by separating the cathode after charging the lithium secondary battery including the cathode, anode, and electrolyte of the above S1 step to SOC 100%, and the delamination index is 3 if delamination occurs in 50% or more of the interface area between the cathode active material layer and the cathode current collector, 2 if delamination occurs in 10% to 50% of the interface area between the cathode active material layer and the cathode current collector, 1 if delamination occurs in 0.1% to 10% of the interface area between the cathode active material layer and the cathode current collector, and 0 if delamination occurs in 0.1% or less of the interface area between the cathode active material layer and the cathode current collector, and the wrinkle index is If wrinkles occur on more than 50% of the surface area of the negative active material layer, it is 3; if wrinkles occur on 10% to 50% of the surface area of the negative active material layer, it is 2; if wrinkles occur on 0.1% to 10% of the surface area of the negative active material layer, it is 1; and if wrinkles occur on 0.1% or less of the surface area of the negative active material layer, it is 0. Claim 3 A method for evaluating the quality of a cathode according to paragraph 2, wherein the above-mentioned good product is a cathode having a detachment index of 1 or less. Claim 4 A method for evaluating the quality of a cathode according to paragraph 2, wherein the above-mentioned good product is a cathode having a wrinkle index of 1 or less. Claim 5 In claim 1, the above reference value comprises the steps of: preparing a plurality of cathode specimens comprising a cathode current collector and a cathode active material layer located on the cathode current collector and comprising a silicon-based cathode active material; measuring the adhesion force F1 between the cathode current collector and the cathode active material layer for each of the plurality of cathode specimens; and immersing each of the plurality of cathode specimens in liquid nitrogen and then measuring the adhesion force (F2) between the cathode current collector and the cathode active material layer. A method for evaluating the quality of a cathode, comprising the step of deriving a reference value from a database obtained by measuring an adhesion index defined by Equation 1 and a risk level defined by Equation A below for each of the plurality of cathode specimens. [Equation A] Risk Level = Delamination Index + Wrinkle Index In Equation A, the delamination index and the wrinkle index are measured by separating each of the cathode specimens after charging a lithium secondary battery containing a positive electrode and an electrolyte to SOC 100% for each of the plurality of cathode specimens, and the delamination index is 3 if delamination occurs in 50% or more of the interface area between the cathode active material layer and the cathode current collector, 2 if delamination occurs in 10% to 50% of the interface area between the cathode active material layer and the cathode current collector, 1 if delamination occurs in 0.1% to 10% of the interface area between the cathode active material layer and the cathode current collector, and the interface area between the cathode active material layer and the cathode current collector If delamination occurs at 0.1% or less, it is 0, and the above wrinkle index is 3 if wrinkles occur at 50% or more of the surface area of the negative electrode active material layer, 2 if wrinkles occur at 10% to 50% of the surface area of the negative electrode active material layer, 1 if wrinkles occur at 0.1% to 10% of the surface area of the negative electrode active material layer, and 0 if wrinkles occur at 0.1% or less of the surface area of the negative electrode active material layer. Claim 6 A method for evaluating the quality of a cathode according to claim 5, wherein the above reference value is set as the minimum value among the adhesion strength indices of cathode specimens in which the risk level satisfies the target range in the above database. Claim 7 In paragraph 6, the above target range is a method for evaluating the quality of a cathode in which the above risk level is 2 or less. Claim 8 A method for evaluating the quality of a cathode according to claim 1, wherein step S3 involves immersing the cathode in liquid nitrogen at -210°C to -180°C and then measuring the adhesion strength (F2) between the cathode current collector and the cathode active material layer. Claim 9 A method for evaluating the quality of a cathode according to claim 1, wherein the S3 step involves immersing the cathode in liquid nitrogen for 5 to 15 minutes and then measuring the adhesion force (F2) between the cathode current collector and the cathode active material layer. Claim 10 A method for evaluating the quality of a cathode according to claim 1, wherein the silicon-based cathode active material comprises a Si / C composite. Claim 11 A method for evaluating the quality of a cathode according to claim 1, wherein the silicon-based cathode active material is included in an amount of 5 to 15 weight percent based on the total weight of the cathode active material layer. Claim 12 A method for manufacturing a lithium secondary battery, comprising: a step of manufacturing a negative electrode including a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector and including a silicon-based negative electrode active material; a step of evaluating the quality of the negative electrode using a quality evaluation method of the negative electrode according to claim 1; and a step of manufacturing a lithium secondary battery including a negative electrode evaluated as good and a positive electrode facing the negative electrode. Claim 13 A method for manufacturing a lithium secondary battery according to claim 12, wherein the cathode has a risk level defined by the following formula A of 2 or less. [Formula A] Risk level = Delamination index + Wrinkle index. In the above formula A, the delamination index and the wrinkle index are measured by separating the cathode after charging the lithium secondary battery comprising the cathode, anode, and electrolyte to SOC 100%, and the delamination index is 3 if delamination occurs at 50% or more of the interface area between the cathode active material layer and the cathode current collector, 2 if delamination occurs at 10% to 50% of the interface area between the cathode active material layer and the cathode current collector, 1 if delamination occurs at 0.1% to 10% of the interface area between the cathode active material layer and the cathode current collector, and 0 if delamination occurs at 0.1% or less of the interface area between the cathode active material layer and the cathode current collector, and the wrinkle index is 50% of the surface area of the cathode active material layer If wrinkles occur above, it is 3; if wrinkles occur in 10% to 50% of the surface area of the negative electrode active material layer, it is 2; if wrinkles occur in 0.1% to 10% of the surface area of the negative electrode active material layer, it is 1; and if wrinkles occur in 0.1% or less of the surface area of the negative electrode active material layer, it is 0. Claim 14 A method for manufacturing a lithium secondary battery according to claim 12, wherein the silicon-based negative electrode active material comprises a Si / C composite. Claim 15 A method for manufacturing a lithium secondary battery according to claim 12, wherein the silicon-based negative electrode active material is included in an amount of 5 to 15 weight percent based on the total weight of the negative electrode active material layer. Claim 16 A cathode comprising: a cathode current collector; and a cathode active material layer located on the cathode current collector and comprising a silicon-based cathode active material; wherein the adhesive strength index value defined by the following Equation 1 is 4.0 gf or higher. [Equation 1] Adhesive strength index (unit: gf) = F2 - F1 In the above Equation 1, F1 (unit: gf) is the adhesive strength between the cathode current collector and the cathode active material layer, and F2 (unit: gf) is the adhesive strength between the cathode current collector and the cathode active material layer after immersing the cathode in liquid nitrogen. Claim 17 In claim 16, the silicon-based negative electrode active material comprises a Si / C composite, forming a negative electrode. Claim 18 In claim 16, the silicon-based negative electrode active material is included in an amount of 5% to 15% by weight based on the total weight of the negative electrode active material layer, forming a negative electrode. Claim 19 In claim 16, a cathode having a risk level defined by the following formula A of 2 or less. [Formula A] Risk level = Delamination index + Wrinkle index. In the above formula A, the delamination index and the wrinkle index are measured by separating the cathode after charging the lithium secondary battery comprising the cathode, anode, and electrolyte to SOC 100%, and the delamination index is 3 if delamination occurs in 50% or more of the interface area between the cathode active material layer and the cathode current collector, 2 if delamination occurs in 10% to 50% of the interface area between the cathode active material layer and the cathode current collector, 1 if delamination occurs in 0.1% to 10% of the interface area between the cathode active material layer and the cathode current collector, and 0 if delamination occurs in 0.1% or less of the interface area between the cathode active material layer and the cathode current collector. The wrinkle index is 3 if wrinkles occur in 50% or more of the surface area of the cathode active material layer. It is 3, and if wrinkles occur in 10% to 50% of the surface area of the negative active material layer, it is 2, if wrinkles occur in 0.1% to 10% of the surface area of the negative active material layer, it is 1, and if wrinkles occur in 0.1% or less of the surface area of the negative active material layer, it is 0. Claim 20 In Clause 19, the cathode having a detachment index of 1 or less. Claim 21 In Clause 19, the above wrinkle index is 1 or less, a cathode. Claim 22 A lithium secondary battery comprising a negative electrode, a positive electrode, and an electrolyte according to any one of claims 16 to 21.
